Toner, toner manufacturing method and image forming method
By optimizing the surface coverage of fatty acid metal salt on toner particles, the issues of development streaks in high humidity and image damage in low humidity are addressed, achieving improved toner performance across varying environmental conditions.
Patent Information
- Application Number
- JP2023115035
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-07-13
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2043-07-13
AI Technical Summary
Existing toners face issues with development streaks in high temperature and high humidity environments and image damage (button-falling phenomenon) in low temperature and low humidity environments, due to inadequate crystallization of monoester wax on the toner particles.
The toner particles are formulated with a specific coverage rate of fatty acid metal salt on their surface, determined by X-ray photoelectron spectroscopy and scanning electron microscopy, to promote the crystallization of amorphous monoester wax components and prevent desorption in different environmental conditions.
This formulation effectively suppresses development streaks in high temperature and high humidity environments while preventing image damage in low temperature and low humidity environments, ensuring consistent high-quality image output.
Smart Images

Figure 0007665689000011 
Figure 0007665689000012 
Figure 0007665689000013
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a toner used in an electrophotographic image forming apparatus, a method for producing the toner, and an image forming method. [Background technology]
[0002] In recent years, there has been a demand for faster operation and higher image quality in electrophotographic image forming apparatuses such as copiers and printers. In addition, due to global efforts to reduce environmental impact, there is an increased demand for energy-saving and longer-lasting products. In addition, regarding the transportation environment from when toner is manufactured to when it is used by consumers, maritime transportation that includes the equator is sometimes used, and the toner needs to continue to provide high-quality images even after undergoing harsh transportation conditions of high temperature and high humidity. In order to satisfy these requirements, the toner is required to have excellent low-temperature fixing property, and also to have storage stability and durability that enable high-quality images to be output even when used for a long period of time after being subjected to harsh transportation environments.
[0003] In order to obtain a toner with excellent low-temperature fixing ability, the use of monoester wax as a release agent in the toner has been investigated. The monoester wax melts and liquefies with the binder resin of the toner when heated, and the melt viscosity of the toner decreases, resulting in a toner with excellent low-temperature fixing ability. Patent Document 1 discloses a toner characterized in that fine particles containing a fatty acid metal salt are present on the surface of toner particles containing a binder resin, and also discloses that a monoester wax can be used as a release agent. Patent Document 2 discloses a toner for developing electrostatic images, which contains toner particles, lubricating particles, and opposite polarity particles having an opposite polarity to the lubricant particles, and which contains composite particles in which the opposite polarity particles are fixed to the surfaces of the lubricant particles to form a composite. It also discloses that a monoester wax can be used as a release agent. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-009250 [Patent Document 2] JP 2018-054705 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the above-mentioned document, the melting property of the toner is improved by using a monoester wax as a release agent. However, when the amount of fatty acid metal salt added is small, if images are continuously output in a high-temperature and high-humidity environment after storage in a transportation mode assuming transportation in a high-temperature and high-humidity environment, development streaks occur in the transport direction of the recording medium as the number of output sheets increases. On the other hand, when the amount of fatty acid metal salt added is large, the above-mentioned development streaks can be improved. However, when images are continuously output in a low temperature and low humidity environment, as the number of output sheets increases, image defects (dripping phenomenon) occur due to toner detachment from the developer carrier. As described above, the toner of the above document has room for improvement in terms of both suppressing development streaks when images are continuously output in a high-temperature, high-humidity environment after having been subjected to a harsh transportation environment of a high-temperature, high-humidity environment, and suppressing dripping when images are continuously output in a low-temperature, low-humidity environment.
[0006] The present disclosure provides a toner that has good low-temperature fixing ability and at the same time has excellent durability even after being subjected to a harsh transportation environment of high temperature and high humidity. To provide a toner which can suppress development streaks when images are continuously output in a high-temperature, high-humidity environment, and can also suppress dripping when images are continuously output in a low-temperature, low-humidity environment. [Means for solving the problem]
[0007] The present disclosure relates to a toner having toner particles containing a binder resin, the toner particles contain a monoester wax; A fatty acid metal salt A is present on the surface of the toner particles, The coverage rate of the surface of the toner particle with the fatty acid metal salt A, which is determined by X-ray photoelectron spectroscopy, is defined as X(A); When the coverage rate of the surface of the toner particle with the fatty acid metal salt A, which is determined by image analysis using a scanning electron microscope, is S(A), The toner relates to a toner in which X(A) and S(A) satisfy the following formulae (1), (2) and (3). S(A)≧0.03 (1) X(A)≦0.250 (2) 0.248≦S(A) / X(A)≦1.000 (3) Effect of the Invention
[0008] According to the present disclosure, it is possible to provide a toner that has good low-temperature fixing properties, and at the same time, after undergoing a harsh transportation environment of a high temperature and high humidity environment, suppresses development streaks when images are continuously output in a high temperature and high humidity environment, and suppresses dripping when images are continuously output in a low temperature and low humidity environment. [Brief description of the drawings]
[0009] [Figure 1] Schematic diagram of the mixing treatment device [Diagram 2] Schematic diagram of the stirring member [Diagram 3] Example of a developing device [Figure 4] Example of a single-component contact development type image forming device DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The description of a numerical range such as "XX to YY" or "XX to YY" means a numerical range including the lower and upper limits, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined.
[0011] The present inventors conducted extensive research into a toner that has good low-temperature fixing properties, and at the same time, after undergoing a harsh transportation environment of a high temperature and high humidity environment, can suppress development streaks when images are continuously output in a high temperature and high humidity environment, and can suppress dripping when images are continuously output in a low temperature and low humidity environment.
[0012] To date, toners that use monoester wax as a release agent have been considered as an approach to improving the low-temperature fixability of toners. This is because monoester wax has high compatibility with binder resins, and when heat is applied, the monoester wax plasticizes the binder resin, lowering the melt viscosity of the toner, allowing it to be fixed to media such as paper even at low temperatures.
[0013] However, when the toner particles are exposed to harsh environments of high temperature and high humidity during transportation, the amorphous components with high molecular mobility and the low-melting-point components with insufficient crystallization of the monoester wax contained in the toner particles tend to bleed out onto the toner particle surface. Some of the bled components remain amorphous on the toner particle surface without crystallizing.
[0014] On the other hand, when images are output continuously for a long period of time in a harsh environment of high temperature and humidity, the temperature of the toner storage container tends to rise, which tends to be more noticeable in the developing nip where the toner and the developing member rub against each other.
[0015] As a result, when images are output continuously for a long time under a high temperature and humidity environment after being transported in the above-mentioned harsh environment, the amorphous components of the wax that have exuded onto the surface of the toner particles in the developing nip become the starting points for the toner to fuse to the developing member, and it has been found that the formation of toner aggregates on the developing member causes development streaks in the conveying direction of the recording medium. In response to this, the present inventors have conducted further studies and have found that in order to suppress the above-mentioned development streaks, it is effective to have a certain amount of fatty acid metal salt present on the surface of the toner particles.
[0016] The fatty acid metal salt is a material having a long-chain alkyl group, which has a structural similarity to the alkyl group constituting the monoester wax. It is also a material that is easily deformed and has ductility. As mentioned above, it is believed that the monoester wax contained in the toner particles will seep out to the surface of the toner particles as an amorphous component under the severe transportation environment of high temperature and high humidity. In this case, it is believed that the presence of the fatty acid metal salt on the surface of the toner particles causes the fatty acid metal salt to act as a crystal nucleating agent for the monoester wax, thereby improving the crystallization speed and degree of crystallization of the amorphous components of the exuded monoester wax. As a result, the exuded components of the wax crystallized using the fatty acid metal salt as a nucleus have a high melting point, making them less likely to become a starting point for the toner to fuse to the developing member, thereby suppressing the occurrence of the above-mentioned development streaks.
[0017] On the other hand, it has become clear that when a toner containing a fatty acid metal salt in an amount necessary to suppress development streaks is used and output is performed continuously for a long period of time in a low-temperature, low-humidity environment, a new image defect (dripping) occurs due to the toner detaching from the developer carrier.
[0018] In a low-temperature, low-humidity environment, the viscoelasticity of the binder resin on the toner particle surface tends to increase, and the adhesive force between the toner particle surface and the fatty acid metal salt tends to decrease. Therefore, in a low-temperature, low-humidity environment, when the toner and the developing member are rubbed against each other in the development nip, the fatty acid metal salt is likely to migrate from the toner particle surface to the developing member, causing contamination of the developing member. The inventors believe that when contamination of components progresses due to long-term continuous output, the toner is not sufficiently charged in the developing nip, which results in a weakening of the electrostatic adhesion between the toner and the developer carrier, causing the toner to detach from the developer carrier and drip.
[0019] As a result of intensive research, the inventors have found that in order to suppress development streaks in a high-temperature, high-humidity environment and to suppress dripping in a low-temperature, low-humidity environment after exposure to harsh transport environments of high temperature and high humidity, it is important to precisely control the state of fatty acid metal salts on the toner particle surfaces.
[0020] First, to suppress development streaks, it is important to promote the crystallization of the amorphous components of the monoester wax that has exuded to the toner particle surface under harsh transport conditions, and to reduce the wax components that exist in an amorphous state on the toner particle surface. In other words, it is necessary to increase the contact opportunity between the fatty acid metal salt, which acts as a crystal nucleating agent, and the exuded wax on the outermost surface of the toner particles. In other words, it is important to control not the amount of fatty acid metal salt contained in the toner, but the coverage rate of the toner particle surface that is in contact with the toner particle surface by fatty acid metal salt. By utilizing the spreadability of fatty acid metal salt and controlling this coverage rate to a certain value or higher, it was discovered that the amorphous components of the wax that have seeped out onto the toner particle surface can be crystallized over a wide area of the toner particle surface, thereby suppressing development streaks.
[0021] Next, regarding the suppression of dripping, when the toner and the developing member are rubbed in the developing nip, the fatty acid metal salt is prevented from migrating from the surface of the toner particles to the developing member, thereby preventing the developing member from being contaminated. In the developing nip, the toner rolls as it passes through, so stress is applied in the tangential direction and normal direction of the toner when the toner is considered as a sphere, and it is thought that the force in the tangential direction of the toner in particular affects the migration of the fatty acid metal salt. In other words, it is believed that if the fatty acid metal salt adheres to the toner particle surface with some height, it will tend to receive a greater force in the tangential direction of the toner, and therefore the fatty acid metal salt will tend to migrate to the developing member due to friction.In other words, it was discovered that by controlling the amount of fatty acid metal salt to a constant amount and then using its extensibility to control the presence of the fatty acid metal salt to a desired coating state on the toner particle surface, it is possible to suppress the migration of the fatty acid metal salt to the developing member and suppress the occurrence of dripping. From the above, the above-mentioned performance can be imparted by having the toner particles contain a binder resin and a monoester wax, and a fatty acid metal salt on the surface of the toner particles, and by precisely controlling the coating state and the presence state of the fatty acid metal salt on the surface of the toner particles.
[0022] The present disclosure relates to a toner having toner particles containing a binder resin, the toner particles contain a monoester wax; A fatty acid metal salt A is present on the surface of the toner particles, The coverage rate of the surface of the toner particle with the fatty acid metal salt A, which is determined by X-ray photoelectron spectroscopy, is defined as X(A); When the coverage rate of the surface of the toner particle with the fatty acid metal salt A, which is determined by image analysis using a scanning electron microscope, is S(A), The toner relates to a toner in which X(A) and S(A) satisfy the following formulae (1), (2) and (3). S(A)≧0.03 (1) X(A)≦0.250 (2) 0.248≦S(A) / X(A)≦1.000 (3)
[0023] The toner will now be described. The coverage rate of the surface of the toner particles by the fatty acid metal salt A, which is determined by X-ray photoelectron spectroscopy, is designated as X(A). The coverage rate of the surface of the toner particles by the fatty acid metal salt A, which is determined by image analysis using a scanning electron microscope, is designated as S(A). S(A) satisfies the following formula (1). S(A)≧0.03 (1) The above formula (1) indicates that 3% or more by area of the surface of the toner particles is covered with the fatty acid metal salt A. The inventors believe that S(A) represents the planar coverage rate on the toner surface.
[0024] As described above, in order to suppress development streaks that occur when images are continuously output under a high-temperature, high-humidity environment after undergoing a harsh transportation environment of a high-temperature, high-humidity environment, it is necessary to increase the contact opportunity between the fatty acid metal salt A, which acts as a crystal nucleating agent, and the exuded wax on the outermost surface of the toner particles. Controlling S(A) to a large value means controlling the coverage of the toner particle surface by the fatty acid metal salt A to a large value. By controlling S(A) to 0.03 or more, the contact opportunity between the fatty acid metal salt A and the exuded wax on the outermost surface of the toner particle can be increased, making it possible to suppress development streaks.
[0025] S(A) is preferably 0.05 or more, more preferably 0.06 or more, and even more preferably 0.10 or more. From the viewpoint of low temperature fixability, S(A) is preferably 0.30 or less, more preferably 0.25 or less, and even more preferably 0.20 or less. Examples of S(A) include 0.03 to 0.30, 0.05 to 0.25, 0.05 to 0.20, 0.06 to 0.20, and 0.10 to 0.20. S(A) can be controlled by the amount of fatty acid metal salt A added and the external addition conditions of fatty acid metal salt A. This can be done.
[0026] In addition, it is important that X(A) satisfies the following formula (2). X(A)≦0.250 (2) X-ray photoelectron spectroscopy is capable of analyzing elements from the surface of a toner particle to a depth of about 5 nm. The above formula (2) indicates that the content of fatty acid metal salt A contained in the toner particles is 25.0 area % or less in a depth range of about 5 nm from the toner surface. The inventors believe that X(A) indicates the amount of fatty acid metal salt A present on the surface of the toner and in its vicinity, including the depth range. Controlling X(A) to a small value means controlling the content of fatty acid metal salt A in the toner to a small value, which leads to a reduction in the frequency of migration from the toner to the developing member. Specifically, by controlling X(A) to 0.250 or less, the amount of fatty acid metal salt A that migrates to the developing member can be suppressed, and dripping due to contamination of the developing member can be suppressed.
[0027] X(A) is preferably 0.220 or less, more preferably 0.180 or less, and even more preferably 0.150 or less. There is no particular lower limit, but it is preferably 0.010 or more, more preferably 0.030 or more, and even more preferably 0.060 or more. Examples of X(A) include 0.010 to 0.250, 0.030 to 0.220, 0.060 to 0.180, and 0.060 to 0.150. X(A) can be controlled by the number of parts of fatty acid metal salt A added.
[0028] In addition, X(A) and S(A) must satisfy the following formula (3). 0.248≦S(A) / X(A)≦1.000 (3) The above formula (3) indicates that in the above depth range of about 5 nm from the toner surface, the coverage rate of the fatty acid metal salt A on the toner particle surface relative to the content of fatty acid metal salt A is 24.8% or more and 100.0% or less.
[0029] S(A) is the planar coverage rate on the toner surface, and X(A) is considered to represent the amount of fatty acid metal salt A including a certain depth range. Therefore, the value of S(A) / X(A) being in the above range indicates that the coverage rate of fatty acid metal salt A on the toner particle surface is somewhat large relative to the content of fatty acid metal salt A in the toner. In other words, the larger the value of S(A) / X(A), the less the fatty acid metal salt A present on the toner particle surface overlaps, indicating that fatty acid metal salt A is attached in a planar manner. On the other hand, the smaller the value of S(A) / X(A) is below the above lower limit, the more fatty acid metal salt A is overlapped and attached three-dimensionally to the toner surface. Therefore, by controlling S(A) / X(A) to 0.248 to 1.000, the coverage rate of the fatty acid metal salt A on the toner particle surface can be increased and the fatty acid metal salt A can be adhered to the toner particle surface in a planar manner. As a result, the migration of the fatty acid metal salt to the developing member can be suppressed, and both development streaks and dripping can be suppressed.
[0030] S(A) / X(A) is preferably from 0.250 to 1.000, more preferably from 0.360 to 1.000, even more preferably from 0.500 to 1.000, even more preferably from 0.600 to 0.960, and particularly preferably from 0.680 to 0.940. S(A) / X(A) can be controlled by the conditions for externally adding the fatty acid metal salt A. When the fatty acid metal salt A is externally added to the toner particles, the fatty acid metal salt A is added while being loosened (while being loosened from secondary particles to primary particles), and then the fatty acid metal salt A is added so as to be spread out, so that S(A) / X(A) can be easily controlled to 0.248 or more.
[0031] More specifically, the Henschel Mixer FM10C (HM) (Nippon Coke Engineering Co., Ltd.) It is possible to increase S(A) / X(A) by externally adding a fatty acid metal salt using a mixer and then further adding it using the apparatus shown in Figure 2. It is also possible to decrease S(A) / X(A) by externally adding the fatty acid metal salt using only a Henschel mixer FM10C(HM) (Nippon Coke and Engineering Co., Ltd.) or by externally adding the fatty acid metal salt using a Henschel mixer FM10C(HM) (Nippon Coke and Engineering Co., Ltd.) after using the apparatus shown in Figure 2.
[0032] <Ester wax> The toner particles contain a monoester wax. The monoester wax is, for example, a compound having one ester bond in the molecule. The monoester wax is preferably at least one compound selected from the group consisting of monoester waxes represented by formula (4). [ka]
[0033] In formula (4), R 51 and R 52 R each independently represents a linear alkyl group having 14 to 24 carbon atoms (preferably 16 to 22, and more preferably 17 to 22). 51 The number of carbon atoms in the linear alkyl group of R is preferably 16 to 18. 52 The linear alkyl group preferably has 20 to 24 carbon atoms.
[0034] That is, the monoester wax is preferably a condensation product of a fatty acid F1 and an alcohol A1, the fatty acid F1 being preferably a monocarboxylic acid and the alcohol A1 being preferably a fatty acid monoalcohol. The fatty acid F1 is preferably an aliphatic monocarboxylic acid having 16 to 22 carbon atoms (preferably 16 to 20, more preferably 17 to 19), and the alcohol A1 is preferably an aliphatic monoalcohol having 16 to 24 carbon atoms (preferably 20 to 24, more preferably 20 to 22).
[0035] Examples of the monoester wax represented by formula (4) include palmityl palmitate, stearyl palmitate, behenyl palmitate, palmityl stearate, stearyl stearate, behenyl stearate, palmityl behenate, stearyl behenate, and behenyl behenate. Among the above monoester waxes, stearyl behenate, behenyl behenate, and behenyl stearate are preferred as the monoester wax, since they have the melting point and molecular weight in the preferred ranges described below. Behenyl stearate is particularly preferred.
[0036] The melting point of the monoester wax is preferably 60°C or higher and 90°C or lower, more preferably 65°C or higher and 85°C or lower, and even more preferably 65°C or higher and 70°C or lower. The molecular weight of the monoester wax is preferably 500 or more and 900 or less, and more preferably 550 or more and 850 or less.
[0037] The SP value of the monoester wax is preferably 8.30 to 8.80, and more preferably 8.45 to 8.65. The unit of the SP value is (cal / cm 3 ) 0.5 It is. The content of the monoester wax is preferably 1.0 parts by mass or more and 40.0 parts by mass or less, more preferably 3.0 parts by mass or more and 30.0 parts by mass or less, even more preferably 5.0 parts by mass or more and 25.0 parts by mass or less, and even more preferably 15.0 parts by mass or more and 25.0 parts by mass or less, relative to 100.0 parts by mass of the binder resin.
[0038] <Fatty acid metal salt A> The toner contains a fatty acid metal salt A on the surface of the toner particles. The fatty acid metal salt A is preferably a salt of fatty acid F2 and a metal. The fatty acid metal salt A is preferably a salt of at least one metal selected from the group consisting of zinc, calcium, magnesium, aluminum, and lithium, and fatty acid F2. The metal is more preferably at least one metal selected from the group consisting of zinc, aluminum, and calcium, even more preferably at least one metal selected from the group consisting of zinc and aluminum, and even more preferably zinc. When these are used, the effect of suppressing development streaks and dripping becomes more remarkable.
[0039] The fatty acid F2 of the fatty metal salt A is preferably a higher fatty acid having 8 to 28 carbon atoms (more preferably 12 to 22, and even more preferably 12 to 18). For example, it is a linear saturated fatty acid. The metal is preferably a polyvalent metal having a valence of 2 or more. That is, the fatty acid metal salt A is preferably a fatty acid metal salt of a polyvalent metal having a metal valence of divalent or more (preferably divalent or trivalent, more preferably divalent) and a fatty acid F2 having a carbon number of 8 to 28 (more preferably 12 to 22, even more preferably 12 to 18). The carbon number of the fatty acid F2 may be preferably 16 to 20.
[0040] It is preferable to use a fatty acid having 8 or more carbon atoms since good electrostatic charge can be obtained. If the number of carbon atoms of the fatty acid F2 is 28 or less, the melting point of the fatty acid metal salt A is not too high, and fixing property is not easily impaired. Stearic acid is particularly preferable as the fatty acid F2. The divalent or higher polyvalent metal preferably contains zinc.
[0041] The fatty acid metal salt A is exemplified by at least one selected from the group consisting of zinc stearate, calcium stearate, magnesium stearate, aluminum stearate, lithium stearate, and other metal stearates, and zinc laurate. The fatty acid metal salt A is more preferably at least one compound selected from the group consisting of zinc stearate and aluminum stearate, and even more preferably zinc stearate.
[0042] The content of the fatty acid metal salt A is preferably 0.06 parts by mass to 0.25 parts by mass, more preferably 0.08 parts by mass to 0.22 parts by mass, and even more preferably 0.10 parts by mass to 0.20 parts by mass, relative to 100 parts by mass of the toner particles. If the amount added is 0.06 parts by mass or more, the effect of adding the fatty acid metal salt A can be obtained. If the amount added is less than 0.20 parts by mass, contamination of the developing member is suppressed, and image defects such as dripping are less likely to occur.
[0043] The volumetric median diameter (D50s) of the fatty acid metal salt A is preferably 0.1 to 3.0 μm, more preferably 0.1 to 2.0 μm. By making it 0.1 μm or more, when added externally, the fatty acid metal salt A spreads on the surface of the toner particles without being too embedded in the toner particles. Therefore, the crystallization of the ester wax can be effectively performed on the surface of the toner particles, so that development streaks can be further suppressed. In addition, by making it 3.0 μm or less, adhesion to the developing member is suppressed, so that dripping can be further suppressed.
[0044] The adhesion rate (%) of the fatty acid metal salt A to the toner particles is preferably 20 to 100, more preferably 25 to 100, even more preferably 40 to 75, and even more preferably 45 to 70. Within the above range, contamination of components by the fatty acid metal salt A can be suppressed, and dripping can be further suppressed. By controlling the mechanical impact force (stirring peripheral speed and time) in the external addition step of the fatty acid metal salt A (the step of mixing the toner particles and the fatty acid metal salt A), the adhesion rate of the fatty acid metal salt A can be controlled within a preferred range.
[0045] The SP value of the alkyl chain of the fatty acid metal salt is preferably 8.18 to 8.30, more preferably 8.20 to 8. .30 is more preferable. The unit of SP value is (cal / cm 3 ) 0.5 It is.
[0046] <Difference in alkyl chain length between ester wax and fatty acid metal salt> The monoester wax is preferably a condensate of a fatty acid F1 and an alcohol A1, and the fatty acid metal salt A is preferably a salt of a fatty acid F2 and a metal. In this case, it is preferable that at least one of the following (a) and (b) is satisfied. (a) The difference between the carbon number of fatty acid F1 and the carbon number of fatty acid F2 is 2 or less. (b) The difference between the carbon number of alcohol A1 and the carbon number of fatty acid F2 is 2 or less. The difference between the carbon number of the fatty acid F1 and the carbon number of the fatty acid F2 may be 2 or less, and the difference between the carbon number of the alcohol A1 and the carbon number of the fatty acid F2 may be 2 or less. When the difference is 2 or less, the crystal nucleating effect of the fatty acid metal salt A is more effectively exerted, and the crystallization of the exuded components of the monoester wax that have exuded to the toner particle surface during transportation is promoted, so that development streaks can be more effectively suppressed. More preferably, the difference between the carbon number of fatty acid F1 and the carbon number of fatty acid F2 is 2 or less. The difference is even more preferably 1 or less, and even more preferably 0.
[0047] <Release agent> The toner particles may contain a known wax as a release agent other than the above monoester wax. Examples of the release agent include petroleum waxes and their derivatives, such as paraffin wax, microcrystalline wax, and petrolatum, montan wax and its derivatives, hydrocarbon waxes and their derivatives produced by the Fischer-Tropsch process, polyolefin waxes and their derivatives, such as polyethylene, natural waxes and their derivatives, such as carnauba wax and candelilla wax, and the derivatives include oxides, block copolymers with vinyl monomers, and graft modified products. These can be used alone or in combination. The toner particles preferably contain a hydrocarbon wax. The content of the release agent other than the monoester wax is preferably 0.1 to 20 parts by mass, more preferably 1 to 10 parts by mass, based on 100 parts by mass of the binder resin.
[0048] <Inorganic fine particles> The toner particles preferably contain inorganic fine particles such as metal fine particles. The toner particles more preferably contain inorganic fine particles that have been hydrophobized. By containing inorganic fine particles in the toner particles, it is possible to suppress embedding of external additives in the toner particles during long-term printing, and improve durability.
[0049] The inorganic fine particles include oxides of metals such as Fe, Si, Ti, Sn, Zn, Al, and Ce, and known fine particles can be used. The hydrophobic treatment is achieved by covering the surface of the inorganic fine particles with a treatment agent having an alkyl group. The inorganic fine particles are preferably surface-treated with a treatment agent having an alkyl group having 4 to 20 carbon atoms (preferably 4 to 14, more preferably 6 to 12). For example, the inorganic fine particles are preferably inorganic fine particles having an alkyl group having 4 to 20 carbon atoms (preferably 4 to 14, more preferably 6 to 12) on the surface.
[0050] The hydrophobic treatment agent is not particularly limited as long as it contains an alkyl group, and examples thereof include silane coupling agents, alkyl-modified silicones, and titanium coupling agents. The hydrophobic treatment agent is preferably a silane coupling agent. The silane coupling agent will be described later.
[0051] It is preferable to carry out the coating treatment using 4 to 20 parts by mass of the treatment agent per 100 parts by mass of inorganic fine particles. It is preferable to use 5 to 15 parts by mass. The method for treating the surface of inorganic fine particles is not particularly limited as long as it is a treatment method using a surface hydrophobic treatment agent. For example, the wet method is to disperse the powder to be treated in a solvent such as water or an organic solvent using a mechanochemical mill such as a ball mill or a sand grinder, mix the hydrophobic treatment agent, remove the solvent, and dry; the dry method is to mix the powder to be treated and the hydrophobic treatment agent using a Henschel mixer (Nippon Coke and Engineering Co., Ltd.) or a super mixer (Kawata Co., Ltd.), and then dry; the method is to contact the powder to be treated and the surface hydrophobic treatment agent in a high-speed airflow such as a counter jet mill (manufactured by Hosokawa Micron Corporation) to perform treatment.
[0052] It is more preferable that the hydrophobically treated inorganic fine particles are magnetic. Magnetic materials include magnetic iron oxides, such as magnetite, maghemite, ferrite, and other metal oxides; metals, such as Fe, Co, Ni, or alloys of these metals with metals, such as Al, Co, Cu, Pb, Mg, Ni, Sn, Zn, Sb, Be, Bi, Cd, Ca, Mn, Se, Ti, W, V, and mixtures thereof.
[0053] Among these, magnetite is preferred, and its shape may be polyhedral, octahedral, hexahedral, spherical, needle-like, or scale-like. In order to increase image density, magnetite having a small contact area between magnetic particles, such as hexahedral or spherical shapes, is preferred because it suppresses aggregation. The number average particle size of the primary particles of the magnetic material is preferably 50 nm or more and 500 nm or less, more preferably 100 nm or more and 300 nm or less, and even more preferably 150 nm or more and 250 nm or less.
[0054] The content of the magnetic material is preferably 35 parts by mass or more and 100 parts by mass or less, and more preferably 45 parts by mass or more and 95 parts by mass or less, relative to 100 parts by mass of the binder resin. The content of the magnetic material in the toner can be measured using a thermal analyzer TGA Q5000IR manufactured by PerkinElmer, Inc. The measurement method is to heat the toner from room temperature to 900°C at a temperature increase rate of 25°C / min in a nitrogen atmosphere, and the weight loss from 100°C to 750°C is the weight of the components excluding the magnetic material from the toner, and the remaining weight is the amount of magnetic material.
[0055] The following is an example of a method for producing the magnetic material. An aqueous solution containing ferrous hydroxide is prepared by adding an equivalent or greater amount of alkali, such as sodium hydroxide, to an aqueous solution of ferrous salt. While maintaining the pH of the prepared aqueous solution at pH 7 or higher, air is blown in and the aqueous solution is heated to 70°C or higher to carry out an oxidation reaction of the ferrous hydroxide, thereby first producing seed crystals that will become the core of the magnetic material.
[0056] Next, an aqueous solution containing 1 equivalent of ferrous sulfate based on the amount of alkali added previously to the slurry liquid containing the seed crystals is added. The reaction of ferrous hydroxide is allowed to proceed while air is blown in while maintaining the pH of the liquid at 5 to 10, and magnetic iron oxide particles are grown around the seed crystals as cores. At this time, the shape and magnetic properties of the magnetic material can be controlled by selecting any pH, reaction temperature, and stirring conditions. As the oxidation reaction progresses, the pH of the liquid shifts to the acidic side, but it is preferable not to make the pH of the liquid less than 5. The magnetic material can be obtained by filtering, washing, and drying the magnetic iron oxide particles obtained in this manner by a standard method.
[0057] Although the hydrophobization treatment of the magnetic material is not particularly limited, it is preferable to use a hydrophobization treatment agent having a relatively large carbon number as shown in the formula (I) described later. In addition, it is preferable that the magnetic material is surface-treated using a treatment device described later. This allows the hydrophobic treatment agent to react uniformly with the particle surfaces of the magnetic material, thereby making it possible to develop high hydrophobicity. The magnetic material is preferably a magnetic material that has been hydrophobized using an alkyltrialkoxysilane coupling agent as a hydrophobizing agent represented by the following formula (I). That is, the magnetic material is preferably a product that has been surface-treated with a hydrophobizing agent represented by the following formula (I). C p H 2p+1 -Si-(OC q H 2q+1 )3(I) In formula (I), p represents an integer of 4 to 12 (preferably 6 to 12), and q represents an integer of 1 to 3 (preferably 1 or 2).
[0058] In the above formula (I), when p is 4 or more, sufficient hydrophobicity can be imparted, while when p is 12 or less, the surface of the magnetic material can be uniformly treated, and coalescence of the magnetic material can be suppressed, which is preferable. Examples include n-butyltrimethoxysilane, n-hexyltrimethoxysilane, n-octyltrimethoxysilane, and n-decyltrimethoxysilane.
[0059] Furthermore, by setting p to 4 or more, the affinity between the treatment agent and the monoester wax is improved, and it becomes easier to obtain the crystal nucleating agent effect that promotes the crystallization of the monoester wax after the fixing process. As a result, after continuous output of images, the molten monoester wax can instantly crystallize, and discharge adhesion (discharge sticking), which is the adhesion of sheets of paper to each other on the discharge tray, can be suppressed.
[0060] The SP value of the alkyl chain contained in the hydrophobizing agent is preferably 7.50 to 8.50, more preferably 7.80 to 8.20. The unit of the SP value is (cal / cm 3 ) 0.5 It is.
[0061] The method for the hydrophobization treatment is not particularly limited, but the following method is preferred. It is preferable to carry out the hydrophobization treatment in a dry manner using a wheel-type kneader or a mixing machine, in order to uniformly react the hydrophobization agent with the particle surface of the magnetic material to develop high hydrophobicity, while at the same time leaving some of the hydroxyl groups on the particle surface of the magnetic material intact rather than completely hydrophobizing it. As the wheel-type kneader, Mixmuller (Shinto Kogyo Co., Ltd.), Eirich Mill (Nihon Eirich Co., Ltd.), etc. can be used, and it is preferable to use Mixmuller (Shinto Kogyo Co., Ltd.). When a wheel-type mixer or a mortar and pestle is used, three actions can be achieved: compression, shearing, and spatula action.
[0062] The compression action presses the hydrophobic treatment agent present between the magnetic particles onto the surface of the magnetic material, increasing adhesion and reactivity with the particle surface. The shear action applies shearing force to both the hydrophobic treatment agent and the magnetic material, stretching the hydrophobic treatment agent while breaking up the magnetic material particles and breaking down agglomerates. Furthermore, the stroking action allows the hydrophobic treatment agent present on the magnetic material particle surface to be spread evenly as if stroking with a spatula. By continuously and repeatedly exerting the above three effects, it is possible to disaggregate the magnetic particles and to hydrophobize the surface of each particle evenly while disaggregating them into individual particles without causing them to re-aggregate.
[0063] Normally, hydrophobic treatment agents having a relatively large number of carbon atoms, as represented by general formula (I), tend to be difficult to treat uniformly at the molecular level on the particle surface of the magnetic material because the molecules are large and bulky. However, treatment by the above-mentioned method is preferable because it enables stable treatment.
[0064] When toner is produced by the suspension polymerization method described below, inorganic fine particles (magnetic material) that have been hydrophobized in this way act like a surfactant during the toner production process due to the hydrophobicity of the alkyl substituents and the hydrophilicity of the remaining hydroxyl groups. As a result, the magnetic material is biased toward the surface vicinity of the toner particles. In other words, the inorganic fine particles (preferably magnetic material) are concentrated near the surface of the toner particles. It is preferable that the toner particles are unevenly distributed in the vicinity of the surface of the toner particles. For example, it is preferable that a shell containing inorganic fine particles is present in the vicinity of the surface of the toner particles. In addition, it is preferable that the toner particles are suspension-polymerized toner particles. The presence of the magnetic material near the surface suppresses the embedding of fatty acid metal salt A into toner particles during long-term use, making it easier for fatty acid metal salt A to exert its crystal nucleating effect on the monoester wax throughout long-term use (the latter half of the number of printed pages).
[0065] <Coloring agent> The toner particles may contain a colorant. In addition to the above-mentioned magnetic material, the toner particles may further contain a colorant. As the colorant, known pigments and dyes of black, yellow, magenta, cyan, and other colors can be used without any particular limitation. Black colorants include black pigments such as carbon black. Examples of yellow colorants include yellow pigments and yellow dyes such as monoazo compounds, disazo compounds, condensed azo compounds, isoindolinone compounds, benzimidazolone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include CI Pigment Yellow 74, 93, 95, 109, 111, 128, 155, 174, 180, and 185, and CI Solvent Yellow 162.
[0066] Examples of magenta colorants include magenta pigments and magenta dyes such as monoazo compounds, condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, 238, 254, 269, and CI Pigment Violet 19.
[0067] Examples of cyan colorants include cyan pigments and cyan dyes such as copper phthalocyanine compounds and derivatives thereof, anthraquinone compounds, and basic dye lake compounds. Specifically, examples include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66. The content of the colorant is preferably 1.0 part by mass or more and 20.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin.
[0068] <Charge control agent> The toner particles may contain a charge control agent. Any known charge control agent can be used as the charge control agent. In particular, a charge control agent that can charge quickly and stably maintain a constant charge amount is preferred. As the charge control agent that controls the toner particles to have a negative charge, the following can be mentioned.
[0069] As organometallic compounds and chelating compounds, monoazo metal compounds, acetylacetone metal compounds, aromatic oxycarboxylic acids, aromatic dicarboxylic acids, oxycarboxylic acids and dicarboxylic acid-based metal compounds, as well as aromatic oxycarboxylic acids, aromatic mono- and polycarboxylic acids and their metal salts, anhydrides or esters, phenol derivatives such as bisphenol, etc. are also included. Further examples include urea derivatives, metal-containing salicylic acid compounds, metal-containing naphthoic acid compounds, boron compounds, quaternary ammonium salts, and calixarenes.
[0070] On the other hand, examples of charge control agents that control toner particles to have a positive charge include the following: nigrosine and nigrosine modified with fatty acid metal salts; guanidine compounds; imidazole compounds; quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthosulfonate and tetrabutylammonium tetrafluoroborate, and onium salts such as phosphonium salts that are analogues of these, and lake pigments thereof; triphenylmethane dyes and lake pigments thereof (lake agents include phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide, ferrocyanide, etc.); metal salts of higher fatty acids; and resin-based charge control agents.
[0071] These charge control agents may be contained alone or in combination of two or more. The amount of these charge control agents added is preferably 0.01 parts by mass or more and 10.00 parts by mass or less with respect to 100.00 parts by mass of the polymerizable monomer.
[0072] <External additives> The toner may also contain external additives. As the external additive, any known external additive can be used without any particular limitation. Examples of external additives include raw silica fine particles such as wet process silica and dry process silica, or surface-treated silica fine particles obtained by surface-treating such raw silica fine particles with a treating agent such as a silane coupling agent, a titanium coupling agent, or silicone oil; metal oxide fine particles such as titanium oxide fine particles, aluminum oxide fine particles, zinc oxide fine particles, and tin oxide fine particles, or metal oxide fine particles obtained by hydrophobizing metal oxides; metal complexes of aromatic carboxylic acids such as salicylic acid, alkyl salicylic acid, dialkyl salicylic acid, naphthoic acid, and dicarboxylic acid; clay minerals such as hydrotalcite; fluorine-based resin fine particles such as vinylidene fluoride fine particles and polytetrafluoroethylene fine particles; inorganic fine particles such as calcium carbonate, calcium phosphate, and cerium oxide; and organic fine particles such as polymethyl methacrylate resin, silicone resin, and melamine resin.
[0073] From the viewpoint of fluidity and charging stability, it is preferable to use silica fine particles obtained by subjecting the original silica fine particles to a hydrophobic treatment using silicone oil or the like. The content of the external additive in the toner is preferably 0.1 parts by mass or more and 5.0 parts by mass or less with respect to 100 parts by mass of the toner particles.
[0074] <Manufacturing method> The following is an example of a method for producing a toner, but the method is not limited to this example. Examples of the method for producing the toner include a pulverization method, a polymerization method, for example, a dispersion polymerization method, an association aggregation method, a dissolution suspension method, a suspension polymerization method, an emulsion aggregation method, etc. The suspension polymerization method is more preferable because it is easy to make a magnetic material exist in the vicinity of the surface of the toner particles, and therefore it is easy to obtain a toner having suitable physical properties.
[0075] In the suspension polymerization method, for example, a polymerizable monomer composition is obtained by uniformly dispersing a polymerizable monomer capable of forming a binder resin, a monoester wax, and, if necessary, a magnetic material, a release agent, a polymerization initiator, a crosslinking agent, a charge control agent, and other additives.Then, the obtained polymerizable monomer composition is dispersed and granulated in a continuous layer (e.g., an aqueous phase) containing a dispersion stabilizer using an appropriate stirrer, and a polymerization reaction is carried out using a polymerization initiator to obtain toner particles having a desired particle size. The toner obtained by this suspension polymerization method is hereinafter also called "polymerized toner".
[0076] The polymerizable monomer may include the following. Styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-meth Styrene monomers such as styrene and p-ethylstyrene. Acrylic acid esters such as methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, n-propyl acrylate, n-octyl acrylate, dodecyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, 2-chloroethyl acrylate, and phenyl acrylate. Methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl methacrylate, dodecyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, phenyl methacrylate, dimethylaminoethyl methacrylate, and diethylaminoethyl methacrylate. Other examples of the monomers include acrylonitrile, methacrylonitrile, acrylamide, etc. These monomers may be used alone or in combination.
[0077] Among the above-mentioned monomers, it is preferable to use a styrene-based monomer alone or in combination with other monomers such as acrylic acid esters and methacrylic acid esters, since it is easy to control the toner structure and improve the development characteristics and durability of the toner. In particular, it is more preferable to use styrene and an alkyl acrylate ester or styrene and an alkyl methacrylate ester as the main components. The number of carbon atoms in the alkyl ester is preferably 1 to 8, more preferably 2 to 6. That is, it is preferable that the binder resin contains 50% by mass or more of styrene-acrylic resin, more preferably 80 to 100% by mass, and even more preferably 90 to 100% by mass.
[0078] The polymerization initiator used in the production of toner particles by the polymerization method is preferably one having a half-life of 0.5 to 30 hours during the polymerization reaction. It is also preferable to use an addition amount of 0.5 to 20 parts by mass per 100 parts by mass of the polymerizable monomer. In this way, a polymer having a molecular weight maximum between 5,000 and 50,000 can be obtained, and the toner can be given a preferable strength and suitable melting properties.
[0079] Specific examples of the polymerization initiator include azo or diazo polymerization initiators such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile, and peroxide polymerization initiators such as benzoyl peroxide, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, lauroyl peroxide, t-butyl peroxy 2-ethylhexanoate, t-butyl peroxypivalate, di(2-ethylhexyl)peroxydicarbonate, and di(secondary butyl)peroxydicarbonate. Of these, t-butyl peroxypivalate is preferred.
[0080] When the toner is produced by a polymerization method, a crosslinking agent may be added, and a known crosslinking agent such as divinylbenzene may be used. The amount of the crosslinking agent added is preferably 0.05 parts by mass or more and 15.00 parts by mass or less, more preferably 0.10 parts by mass or more and 10.00 parts by mass or less, even more preferably 0.20 parts by mass or more and 5.00 parts by mass or less, and even more preferably 0.25 parts by mass or more and 0.60 parts by mass or less, relative to 100.00 parts by mass of the polymerizable monomer.
[0081] The polymerizable monomer composition may contain a polar resin. Examples of polar resins include homopolymers of styrene and its substitutes, such as polystyrene and polyvinyltoluene; styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, and styrene. styrene-based copolymers such as styrene-ethyl acrylate copolymer, styrene-butyl acrylate copolymer, styrene-octyl acrylate copolymer, styrene-dimethylaminoethyl acrylate copolymer, styrene-methyl methacrylate copolymer, styrene-ethyl methacrylate copolymer, styrene-butyl methacrylate copolymer, styrene-dimethylaminoethyl methacrylate copolymer, styrene-vinyl methyl ether copolymer, styrene-vinyl ethyl ether copolymer, styrene-vinyl methyl ketone copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-maleic acid copolymer, and styrene-maleic acid ester copolymer; polymethyl methacrylate, polybutyl methacrylate, polyvinyl acetate, polyethylene, polypropylene, polyvinyl butyral, silicone resin, polyester resin, styrene-polyester copolymer, polyacrylate-polyester copolymer, polymethacrylate-polyester copolymer, polyamide resin, epoxy resin, polyacrylic acid resin, terpene resin, and phenol resin.
[0082] These may be used alone or in combination of two or more.Functional groups such as amino groups, carboxy groups, hydroxyl groups, sulfonic acid groups, glycidyl groups, and nitrile groups may be introduced into these polymers.Among these resins, polyester resins are preferred.
[0083] As the polyester resin, it is possible to appropriately select and use a saturated polyester resin, an unsaturated polyester resin, or both. The polyester resin may be a typical one composed of an alcohol component and an acid component, both of which are exemplified below.
[0084] Examples of the dihydric alcohol component include ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, cyclohexanedimethanol, butenediol, octenediol, cyclohexenedimethanol, hydrogenated bisphenol A, or a bisphenol derivative represented by formula (A); a hydrogenated product of a compound represented by formula (A) below, a diol represented by formula (B) below, or a diol of a hydrogenated product of a compound of formula (B). [ka]
[0085] In formula (A), R is an ethylene group or a propylene group, x and y are each an integer of 1 or more, and the average value of x+y is 2-10. [ka]
[0086] As the dihydric alcohol component, the alkylene oxide adduct of bisphenol A is particularly preferred, which is excellent in electrostatic properties and environmental stability and is well-balanced in other electrophotographic properties. In the case of this compound, the average number of moles of alkylene oxide added is preferably 2 or more and 10 or less in terms of fixing property and durability of the toner.
[0087] Examples of the divalent acid component include benzenedicarboxylic acids or anhydrides thereof, such as phthalic acid, terephthalic acid, isophthalic acid, and phthalic anhydride; alkyldicarboxylic acids or anhydrides thereof, such as succinic acid, adipic acid, sebacic acid, and azelaic acid; succinic acid or anhydrides thereof substituted with an alkyl or alkenyl group having 6 to 18 carbon atoms; and unsaturated dicarboxylic acids or anhydrides thereof, such as fumaric acid, maleic acid, citraconic acid, and itaconic acid.
[0088] Furthermore, examples of trihydric or higher alcohol components include glycerin, pentaerythritol, sorbitol, sorbitan, and oxyalkylene ether of novolac-type phenolic resin. Examples of trivalent or higher acid components include trimellitic acid, pyromellitic acid, 1,2,3,4-butanetetracarboxylic acid, benzophenonetetracarboxylic acid, and anhydrides thereof.
[0089] In the polyester resin, the alcohol component preferably accounts for 45 mol % or more and 55 mol % or less when the total of the alcohol component and the acid component is taken as 100 mol %. The polyester resin can be produced using any catalyst, such as a tin-based catalyst, an antimony-based catalyst, or a titanium-based catalyst, but it is preferable to use a titanium-based catalyst.
[0090] In addition, the polar resin preferably has a number average molecular weight of 2,500 or more and 25,000 or less from the viewpoints of developability, blocking resistance, and durability. The acid value of the polar resin is preferably 1.0 mgKOH / g or more and 15.0 mgKOH / g or less, and more preferably 2.0 mgKOH / g or more and 10.0 mgKOH / g or less. The content of the polar resin is preferably 2 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0091] The aqueous medium in which the polymerizable monomer composition is dispersed may contain a dispersion stabilizer. As the dispersion stabilizer, known surfactants, organic dispersants, and inorganic dispersants can be used. Among these, inorganic dispersants are preferably used because they provide dispersion stability due to their steric hindrance, and therefore the stability is not easily lost even when the reaction temperature is changed, and they are easy to wash and do not adversely affect the toner.
[0092] Specific examples of inorganic dispersants include polyvalent metal phosphates such as tricalcium phosphate, magnesium phosphate, aluminum phosphate, zinc phosphate, and hydroxyapatite; carbonates such as calcium carbonate and magnesium carbonate; inorganic salts such as calcium metasilicate, calcium sulfate, and barium sulfate; and inorganic compounds such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide.
[0093] The amount of the inorganic dispersant added is preferably 0.2 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the polymerizable monomer. The dispersion stabilizer may be used alone or in combination with a plurality of kinds. Furthermore, a surfactant may be used in combination in an amount of 0.001 parts by mass or more and 0.1 parts by mass or less.
[0094] When an inorganic dispersant is used, it may be used as it is, but in order to obtain finer particles, it may be used after forming fine particles of the inorganic dispersant in an aqueous medium. For example, in the case of tricalcium phosphate, water-insoluble calcium phosphate microparticles can be produced by mixing an aqueous solution of sodium phosphate with an aqueous solution of calcium chloride under high speed stirring, enabling a more uniform and finer dispersion.
[0095] Examples of the surfactant include sodium dodecylbenzene sulfate, sodium tetradecyl sulfate, sodium pentadecyl sulfate, sodium octyl sulfate, sodium oleate, sodium laurate, sodium stearate, and potassium stearate.
[0096] In the step of polymerizing the polymerizable monomer, the polymerization temperature is usually set to a temperature of 40°C or higher, preferably 50°C or higher and 90°C or lower. Thereafter, there is a cooling process in which the polymerization reaction process is terminated by cooling from the reaction temperature of about 50° C. to 90° C. In this case, the cooling may be performed gradually so as to maintain the compatibility of the release agent and the binder resin.
[0097] After the polymerization reaction is completed, a step of heating the dispersion liquid containing the polymerized particles to 95 to 120° C. and maintaining the temperature for 1 to 5 hours may be carried out, followed by a cooling step, which is preferably carried out. In the cooling step, it is preferable to carry out a cooling step at a rate of 50 to 300°C / min (preferably 100 to 300°C / min, more preferably 150 to 250°C / min). This step allows the crystalline material contained in the binder resin to be dispersed in the toner particles in a fine shape. The cooling step may be carried out, for example, to about 20 to 50°C.
[0098] Further, it is preferable to carry out an annealing step thereafter, in which the mixture is held at 40 to 65° C. (preferably 40 to 60° C.) for 1 to 10 hours (preferably 2 to 5 hours). This step can improve the crystallinity of the crystalline material contained in the binder resin.
[0099] The resulting polymer particles are then filtered, washed, and dried by a known method to obtain toner particles. The toner particles are mixed with an external additive and allowed to adhere to the surface of the toner particles to obtain a toner. It is also possible to include a classification process in the manufacturing process to remove coarse powder and fine powder contained in the toner particles.
[0100] The volume average particle diameter (Dv) of the toner is preferably 5.0 μm to 10.0 μm, and more preferably 6.0 μm to 9.0 μm. By setting the volume average particle diameter (Dv) of the toner in the above range, the developability can be sufficiently satisfied. The ratio (Dv / D1) of the volume average particle diameter (Dv) to the number average particle diameter (D1) of the toner is preferably 1.25 or less, and more preferably less than 1.25. The Dv and Dv / D1 of the toner can be controlled by the amount of dispersant, the type of agitator, the rotation speed, etc.
[0101] The weight average molecular weight (Mw) of the binder resin is preferably 10,000 to 300,000, more preferably 15,000 to 260,000, and even more preferably 20,000 to 230,000. When the weight average molecular weight of the binder resin is 300,000 or less, low temperature fixability tends to be improved. When the weight average molecular weight of the binder resin is 10,000 or more, heat resistance storage stability tends to be improved.
[0102] The molecular weight distribution of the binder resin (weight average molecular weight Mw / number average molecular weight Mn) is preferably from 2 to 40, more preferably from 3 to 35, and even more preferably from 3 to 23. When the molecular weight distribution is 40 or less, low-temperature fixability and storage stability tend to be improved. When the molecular weight distribution is 2 or more, There is a tendency for hot offset resistance to be improved.
[0103] <External addition method> It is preferable to have a treatment step of treating the mixture having the toner particles and the fatty acid metal salt A. The processing device used in the processing step is An agitating member having a rotor and a plurality of agitating blades provided on a surface of the rotor; A container having a cylindrical inner circumferential surface that accommodates the stirring member; and a drive unit for applying a rotational drive force to the rotor to rotate the stirring member within the container, The plurality of stirring blades are provided so as to have a gap between each of them and an inner peripheral surface of the container, It is preferable that the multiple stirring blades have a first stirring blade for transporting the mixture introduced into the container in one axial direction of the rotating body by rotation of the stirring member, and a second stirring blade for transporting the mixture in the other axial direction of the rotating shaft.
[0104] As the mixing and processing device for externally mixing the fatty acid metal salt A and the silica fine particles, a known mixing and processing device can be used, but from the viewpoint of controlling the coating state of the fatty acid metal salt A, a device such as that shown in FIG. FIG. 1 is a schematic diagram showing an example of a mixing treatment device that can be used when externally mixing an external additive such as a fatty acid metal salt A. The mixing and processing device is configured such that a shear force is applied to the toner particles and external additives such as fatty acid metal salt A in a narrow clearance area, so that the external additives can be attached to the surfaces of the toner particles while breaking them down from secondary particles to primary particles, or the fatty acid metal salt A can be attached in a spread-out state.
[0105] On the other hand, FIG. 2 is a schematic diagram showing an example of the configuration of a stirring member used in the above-mentioned mixer.
[0106] The external additive mixing step will be described below with reference to FIGS. The mixing processing device for externally mixing the above-mentioned external additives has an agitating member having at least a plurality of agitating blades 33 installed on the surface of a rotor 32, a drive unit 38 for rotating the rotor, and a main casing 31 provided with a gap between the agitating blades 33 and the main casing 31. It is important that the gap (clearance) between the inner circumference of the main casing 31 and the agitator blade 33 is kept constant and small so as to provide a uniform shear to the toner particles and to easily adhere to the surface of the toner particles while breaking down the external additives from secondary particles to primary particles.
[0107] In addition, in this device, the diameter of the inner periphery of the main casing 31 is no more than twice the diameter of the outer periphery of the rotor 32. Fig. 1 shows an example in which the diameter of the inner periphery of the main casing 31 is 1.7 times the diameter of the outer periphery of the rotor 32 (the diameter of the body part (rotor 32) excluding the stirring blade 33 from the stirring member). When the diameter of the inner periphery of the main casing 31 is no more than twice the diameter of the outer periphery of the rotor 32, the processing space in which a force acts on the toner particles is appropriately limited, so that a sufficient impact force is applied to the external additive that has become secondary particles.
[0108] It is also important to adjust the clearance according to the size of the main casing. It is important to set the clearance to about 1% to 5% of the diameter of the inner periphery of the main casing 31 in order to apply sufficient shear to the external additive. Specifically, when the diameter of the inner periphery of the main casing 31 is about 130 mm, the clearance should be about 2 mm to 9 mm, and when the diameter of the inner periphery of the main casing 31 is about 800 mm, the clearance should be about 10 mm to 30 mm.
[0109] The external additive mixing process uses a mixing treatment device, rotates the rotor 32 using the drive unit 38, and stirs and mixes the toner particles and external additives fed into the mixing treatment device, thereby externally mixing the external additives onto the surfaces of the toner particles.
[0110] 2, at least some of the agitating blades 33 are formed as sending agitating blades 33a that send the toner particles and external additives in one axial direction of the rotor 32 as the rotor 32 rotates. At least some of the agitating blades 33 are formed as returning agitating blades 33b that return the toner particles and external additives in the other axial direction of the rotor as the rotor 32 rotates. Here, when the raw material inlet 35 and the product outlet 36 are provided at both ends of the main casing 31 as in Figure 1, the direction from the raw material inlet 35 to the product outlet 36 (to the right in Figure 1) is referred to as the "feed direction".
[0111] 2, the plate surface of the feeding agitating blade 33a is inclined so as to feed the toner particles in a feeding direction 43. On the other hand, the plate surface of the agitating blade 33b is inclined so as to feed the toner particles and the external additives in a return direction 42. The agitating blade 33a and the agitating blade 33b are in a relationship of a first agitating blade and a second agitating blade. As a result, the toner particles are repeatedly fed in the "feed direction" 43 and the "return direction" 42, while the external additives are mixed on the surfaces of the toner particles. The stirring blades 33a and 33b are each a set of multiple members spaced apart in the circumferential direction of the rotor 32. In the example shown in Fig. 2, the stirring blades 33a and 33b are each a set of two members spaced 180 degrees apart from each other on the rotor 32, but the set may also be made up of multiple members, such as three members spaced 120 degrees apart or four members spaced 90 degrees apart.
[0112] In the example shown in FIG. 2, a total of 12 stirring blades 33a and 33b are formed at equal intervals. Furthermore, in Fig. 2, D is the width of the agitating blade, and d is the distance indicating the overlapping portion of the agitating blade. From the viewpoint of efficiently sending toner particles and external additives in the forward and return directions, it is preferable that D is 20% or more and approximately 30% of the length of rotor 32 in Fig. 2. Fig. 2 shows an example where it is 23%. Furthermore, it is preferable that agitating blades 33a and 33b have a certain degree of overlapping portion d between agitating blade 33b and agitating blade 33a when an extension line is drawn vertically from the end position of agitating blade 33a.
[0113] This makes it possible to efficiently apply shear to the external additive in the form of secondary particles. In terms of applying shear, it is preferable that d with respect to D is 10% or more and 30% or less. As for the shape of the blade, other than the shape shown in FIG. 2, as long as it can send toner particles in the forward and return directions and can maintain clearance, it may have a curved shape or a paddle structure in which the tip of the blade is connected to the rotor 32 by a rod-shaped arm.
[0114] The apparatus will be described in detail below with reference to the schematic diagrams of Figs. 1 and 2. The apparatus shown in Fig. 1 is The device comprises a rotor 32 having at least a plurality of stirring blades 33 mounted on its surface, a drive unit 38 that rotates the rotor 32, and a main casing 31 that is provided with a gap between the stirring blades 33. The device further comprises a jacket 34 that is disposed inside the main casing 31 and on the side surface 310 of the rotor end and through which a cooling or heating medium can flow. 1 further has a raw material inlet 35 formed in the upper part of the main casing 31 and a product outlet 36 formed in the lower part of the main casing 31. The raw material inlet 35 is used to introduce toner particles and external additives, and the product outlet 36 is used to discharge the toner that has been mixed with the external additives from the main casing 31 to the outside.
[0115] Furthermore, in the device shown in FIG. 1, an inner piece 316 for the raw material inlet is inserted into the raw material inlet , and an inner piece 317 for the product outlet is inserted into the product outlet . First, the inner piece 316 for the raw material inlet is removed from the raw material inlet 35, and toner particles are fed into the processing space 39 through the raw material inlet 35. Next, an external additive is fed into the processing space 39 through the raw material inlet 35, and the inner piece 316 for the raw material inlet is inserted. Next, the rotor 32 is rotated by the drive unit 38 (41 indicates the direction of rotation), and the material fed above is stirred and mixed by the stirring blades 33 provided on the surface of the rotor 32, for external addition mixing processing.
[0116] The order of feeding may be such that the external additives are first fed through the raw material feeding port 35, and then the toner particles are fed through the raw material feeding port 35. It is preferable to mix the toner particles and the external additives in advance with a mixer such as a Henschel mixer, and then feed the mixture through the raw material feeding port 35 of the device shown in FIG.
[0117] 1 is not particularly limited, but is preferably 1 to 10 minutes, more preferably 2 to 6 minutes, and even more preferably 3 to 5 minutes. If the treatment time is shorter than 1 minute, the fatty acid metal salt A is not sufficiently spread over the toner particle surfaces, and S(A) / X(A) tends to be small. The rotation speed of the stirring member during external mixing is not particularly limited. -3 m 3 In this device, when the shape of the stirring blade 33 is as shown in Fig. 2, the rotation speed of the stirring blade is preferably 500 rpm or more and 2000 rpm or less, and more preferably 800 rpm or more and 1500 rpm or less. By being in the above range, it becomes easier to obtain a coating state of the specific fatty acid metal salt A.
[0118] It is preferable to perform three-stage mixing by mixing the toner particles and silica fine particles once (first stage), adding and mixing the fatty acid metal salt A (second stage), and then mixing (third stage) using the device shown in Figure 1. It is preferable to use a known mixing device such as a Henschel mixer for the first and second stages of mixing.
[0119] After the external additive mixing process is completed, the inner piece 317 for the product discharge port is removed from the product discharge port 36, and the rotor 32 is rotated by the drive unit 38 to discharge the toner from the product discharge port 36. If necessary, the obtained toner is separated into coarse particles using a sieve such as a circular vibration sieve to obtain the toner.
[0120] The image forming method will be described. The image forming method is a charging step of charging the surface of the electrostatic latent image bearing member; an electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the electrostatic latent image bearing member; a developing step of developing the electrostatic latent image with a toner to form a toner image on the surface of the electrostatic latent image carrier; a transfer step of transferring the toner image from the electrostatic latent image carrier to a transfer material with or without an intermediate transfer member; and a fixing step of fixing the toner image transferred onto the transfer material by a heating and pressing means; has. The developing step is preferably a one-component contact developing step.
[0121] (One-component contact development method) The one-component contact development method will be described. FIG. 3 is a schematic cross-sectional view showing an example of a developing device. FIG. FIG. 1 is a schematic cross-sectional view showing an example of an image forming apparatus of the type.
[0122] 3 or 4, the electrostatic latent image carrier 45 on which the electrostatic latent image is formed is rotated in the direction of arrow R1. The toner carrier 47 rotates in the direction of arrow R2 to transport toner 57 to a development area where the toner carrier 47 and the electrostatic latent image carrier 45 face each other. A toner supplying member 48 is in contact with the toner carrier 47, and supplies toner 57 to the surface of the toner carrier 47 by rotating in the direction of arrow R3. The toner 57 is stirred by a stirring member 58.
[0123] Around the electrostatic latent image carrier 45, there are provided a charging member (charging roller) 46, a transfer member (transfer roller) 50, a cleaner container 43, a cleaning blade 44, a fixing device 51, a pickup roller 52, etc. The electrostatic latent image carrier 45 is charged by the charging roller 46. Then, the electrostatic latent image carrier 45 is exposed by irradiating it with laser light by a laser generating device 54, and an electrostatic latent image corresponding to the target image is formed. The electrostatic latent image on the electrostatic latent image carrier 45 is developed with toner 57 in a developing device 49 to obtain a toner image. The toner image is transferred onto a transfer material (paper) 53 by a transfer member (transfer roller) 50 that is in contact with the electrostatic latent image carrier 45 via the transfer material. The transfer of the toner image onto the transfer material may be performed via an intermediate transfer body. The transfer material (paper) 53 carrying the toner image is transported to a fixing device 51, where the toner image is fixed onto the transfer material (paper) 53. In addition, toner 57 that remains partially on the electrostatic latent image carrier 45 is scraped off by a cleaning blade 44 and stored in a cleaner container 43.
[0124] Further, it is preferable that a toner regulating member (reference numeral 55 in FIG. 3) abuts on the toner carrier via toner to regulate the toner layer thickness on the toner carrier. By doing so, high image quality without regulation failure can be obtained. As the toner regulating member that abuts on the toner carrier, a regulating blade is common.
[0125] The base portion, which is the upper side portion of the regulating blade, is fixedly held on the developing device side, and the lower side portion is bent in the forward or reverse direction of the toner carrier against the elastic force of the blade and abutted on the toner carrier surface with an appropriate elastic pressing force. For example, as shown in FIG. 3, the toner regulating member 55 may be fixed to the developing device by sandwiching one free end of the toner regulating member 55 with two fixing members (for example, a metal elastic body, reference numeral 56 in FIG. 3) and fixing it with screws.
[0126] Hereinafter, the measurement methods of each physical property value will be described. <Measurement of Coating Rate X(A) by Fatty Acid Metal Salt A by X-ray Photoelectron Spectroscopy> The coating rate X(A) of the surface of the toner particles with the fatty acid metal salt A is measured by ESCA (X-ray photoelectron spectroscopy analysis) (Quantum 2000 manufactured by ULVAC-PHI, Inc.). As the sample holder, a 75 mm square platen (equipped with screw holes with a diameter of about 1 mm for fixing the sample) attached to the apparatus was used. Since the screw holes of the platen are through holes, the holes are plugged with resin or the like to create a concave portion for powder measurement with a depth of about 0.5 mm. The measurement sample (toner or fatty acid metal salt A alone) is packed into the concave portion with a spatula or the like and polished to prepare a sample.
[0127] The measurement conditions of ESCA are as follows. Analysis method: Narrow analysis X-ray source: Al-Kα X-ray conditions: 100 μ25W15kV Photoelectron capture angle: 45° PassEnergy: 58.70 eV Measurement range: φ diameter 100 μm First, the toner is measured. The quantitative value of the metal atom contained in the fatty acid metal salt A in the toner is calculated using the element peak of the metal in the fatty acid metal salt A. The quantitative value (cps) of the metal element when the toner obtained here is measured is designated as X1. Similarly, elemental analysis of fatty acid metal salt A alone is performed, and the quantitative value (cps) of the metal elements contained in fatty acid metal salt A obtained here is designated as X2. If a sample of fatty acid metal salt A is available, that sample is used for fatty acid metal salt A alone. Fatty acid metal salt A separated from a toner by the following method may also be used. Using the above X1 and X2, X(A) is calculated using the following formula. Coverage rate of toner particle surface by fatty acid metal salt A X(A)(%)=X1 / X2×100
[0128] <Measurement of the content of fatty acid metal salt A in toner> The fatty acid metal salt A is separated from the toner and the content is measured by the following method. 1 g of toner is added to 31 g of chloroform in a vial and dispersed. The dispersion is processed for 30 minutes using an ultrasonic homogenizer to produce a dispersion liquid. The processing conditions are as follows: Ultrasonic processing device: Ultrasonic homogenizer VP-050 (manufactured by Taitec Co., Ltd.) Microchip: Step type microchip, tip diameter φ2mm Microchip tip position: Center of glass vial, 5 mm above the bottom of the vial Ultrasonic conditions: intensity 30%, 30 minutes. During this time, ultrasonic waves are applied while cooling the vial with ice water to prevent the dispersion from heating up. The dispersion liquid was transferred to a glass tube (50 mL) for a swing rotor and centrifuged at 58.33 S in a centrifuge (H-9R; manufactured by Kokusan Co., Ltd.). -1 The mixture is centrifuged for 30 minutes. After centrifugation, the toner is separated into its constituent materials in the glass tube. Each material is extracted and dried under vacuum conditions (40°C / 24 hours). Fatty acid metal salt A is selected and extracted, and the content is measured.
[0129] <Confirmation of the structure of fatty acid metal salt A (number of carbon atoms and metal element of F2)> The structure of the fatty acid metal salt A separated by the above procedure is determined by pyrolysis GCMS in the same manner as in <Identification and molecular weight measurement of monoester wax by mass spectrometry> described below.
[0130] <Measurement of the coverage rate S(A) of the toner particle surface by fatty acid metal salt A using a scanning electron microscope> The coverage rate S(A) of the toner particle surface by fatty acid metal salt A is measured using a scanning electron microscope "S-4800" (product name; manufactured by Hitachi, Ltd.). 100 toner particles are randomly photographed in a field of view magnified up to 50,000 times. From the captured image, the area "A" of the toner region where fatty acid metal salt A is not attached and the area "B" of the toner region where fatty acid metal salt A is attached are measured, and the ratio of the toner region covered with fatty acid metal salt A is calculated [B / (A+B)×100]. The coverage ratio is measured for 100 toner particles, and the arithmetic mean value is taken as the coverage ratio S(A) (area %). The area to which fatty acid metal salt A is attached is judged as follows. In the above toner observation, EDS analysis is performed on each external additive, and whether or not the external additive being analyzed is fatty acid metal salt A is determined based on the presence or absence of peaks of metal elements such as zinc, calcium, magnesium, aluminum, or lithium. The area other than the area where fatty acid metal salt A is attached is defined as the area where fatty acid metal salt A is not attached.
[0131] <Volume-based median diameter (D50s) of fatty acid metal salt A> The volume-based median diameter of fatty acid metal salt A was measured according to JIS Z8825-1 (2001 The measurement is based on the 2010 Recommendation (2010), and the specific details are as follows: The measuring device used was a laser diffraction / scattering particle size distribution measuring device "LA-920" (manufactured by Horiba). A HORIBA LA-920 for Windows (registered trademark) WET (LA-920) Ver. 2.02 software that comes with the LA-920 is used to set the measurement conditions and analyze the measurement data. Ion-exchanged water from which solid impurities have been removed in advance is used as the measurement solvent. The measurement procedure is as follows. (1) Attach the batch type cell holder to the LA-920. (2) A specified amount of ion-exchanged water is placed in a batch cell, and the batch cell is set in the batch cell holder. (3) Stir inside the batch cell using a dedicated stirrer tip. (4) Click the "Refractive Index" button on the "Display Condition Setting" screen and select the file "110A000I" (relative refractive index 1.10). (5) On the "Display Condition Setting" screen, set the particle size standard to the volume standard. (6) After warming up for at least one hour, adjust the optical axis, fine-tune the optical axis, and perform a blank measurement. (7) Put 60 ml of ion-exchanged water into a 100 ml flat-bottom glass beaker, and add 0.3 ml of a solution of "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments made from a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times with ion-exchanged water as a dispersant. (8) Prepare an ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees, and has an electrical output of 120 W. Place 3.3 L of ion-exchanged water in the ultrasonic disperser's water tank, and add 2 ml of Contaminon N to this water tank. (9) The beaker of (7) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the aqueous solution in the beaker is maximized. (10) While the aqueous solution in the beaker in (9) is irradiated with ultrasonic waves, 1 mg of fatty acid metal salt is added little by little to the aqueous solution in the beaker and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. Note that during this process, the fatty acid metal salt may form lumps and float on the surface of the liquid. In this case, the lumps are submerged in the water by shaking the beaker, and ultrasonic dispersion is then performed for 60 seconds. In addition, during ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be between 10°C and 40°C. (11) The aqueous solution in which the fatty acid metal salt prepared in (10) is dispersed is immediately added to the batch cell in small amounts while being careful not to introduce air bubbles, and the transmittance of the tungsten lamp is adjusted to 90% to 95%. Then, the particle size distribution is measured. Based on the obtained volume-based particle size distribution data, the 50% cumulative diameter from the small particle size side is calculated and taken as the median diameter (D50s).
[0132] <Separation of toner particles from toner> If necessary, the various physical properties can be measured using toner particles from which external additives have been removed by the following method. Add 160 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Place 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) in a centrifuge tube (capacity 50 ml). Add 1.0 g of toner to this, and break up any clumps of toner with a spatula or similar. Shake the centrifuge tube at 300 strokes per minute (sold by AS ONE Corporation) for 20 minutes. After shaking, transfer the solution to a glass tube for a swing rotor (50 mL) and centrifuge (H-9R sold by AS ONE Corporation). The separation is performed using a centrifuge (manufactured by Kokusan) at 3500 rpm for 30 minutes. This operation separates the toner particles from the external additives. Visually check that the toner particles and the aqueous solution are sufficiently separated, and collect the toner particles that have separated to the top layer with a spatula or similar. The collected toner particles are filtered through a vacuum filter, and then dried in a dryer for at least one hour to obtain a sample for measurement. This operation is carried out multiple times to ensure the required amount.
[0133] <Identification and molecular weight measurement of monoester waxes by mass spectrometry> Separation of monoester wax from toner The molecular weight of the monoester wax in the toner can be determined by measuring the toner, but it is more preferable to measure it after carrying out a separation operation. The toner is dispersed in ethanol, which is a poor solvent for the toner, and the temperature is raised to a temperature above the melting point of the monoester wax. At this time, pressure may be applied if necessary. By this operation, the monoester wax that has exceeded its melting point is melted and extracted into the ethanol. If pressure is applied in addition to heating, the monoester wax can be separated from the toner by performing solid-liquid separation while still under pressure.
[0134] The extract is then dried and solidified to obtain the monoester wax. The monoester wax can be identified and its molecular weight measured by pyrolysis GCMS using the following equipment and measurement conditions. Mass spectrometer: ThermoFisher Scientific ISQ GC equipment: ThermoFisher Scientific FocusGC Ion source temperature: 250℃ Ionization method: EI Mass range: 50-1000m / z Column: HP-5MS [30m] Pyrolysis equipment: Japan Analytical Industry Co., Ltd. JPS-700 A small amount of the monoester wax separated by the extraction operation and 1 μL of tetramethylammonium hydroxide (TMAH) are added to a pyrofoil at 590°C. The prepared sample is subjected to pyrolysis GCMS measurement under the above conditions, and peaks for the alcohol and carboxylic acid components that make up the monoester wax are obtained. At this time, the alcohol and carboxylic acid components are detected as methylated products due to the action of TMAH, a methylating agent. The molecular weight of the monoester wax can be determined by analyzing the obtained peaks and identifying the structure of the monoester wax.
[0135] When the monoester wax is identified and its molecular weight is measured by the direct introduction method, the following apparatus and measurement conditions can be used. Mass spectrometer: ThermoFisher Scientific ISQ Ion source temperature: 250℃ Electron energy: 70eV Mass range: 50-1000m / z(CI) Reagent Gas: Methane (CI) Ionization method: ThermoFisher Scientific Direct Exposure Probe (DEP), 0mA (10sec)-10mA / sec-1000mA (10sec) The monoester wax separated by the extraction operation is placed directly on the filament of the DEP unit and measured. The molecular ion in the mass spectrum of the main component peak at around 0.5 to 1 minute in the obtained chromatogram is confirmed, and the monoester wax is identified and its molecular weight is determined.
[0136] <Measurement of the melting point of monoester wax> Weigh out 6 mg to 8 mg of monoester wax into the sample holder and place it on the differential scanning calorimeter. A DSC curve is obtained by measuring the temperature from -20°C to 100°C at a rate of 10°C / min using a DSC thermometer (Seiko Instruments Inc., product name: RDC-220). The peak temperature of the endothermic peak in the DSC curve is taken as the melting point.
[0137] <Method for measuring the glass transition temperature of toner> The glass transition temperature of the toner is measured in accordance with ASTM D3418-97. Specifically, 10 mg of the toner obtained by drying is weighed out and placed in an aluminum pan. An empty aluminum pan is used as a reference. Using a differential scanning calorimeter (manufactured by SII NanoTechnology, Inc., product name: DSC6220), the glass transition temperature of the weighed out toner is measured in accordance with ASTM D 3418-97 under the conditions of a measurement temperature range of 0°C to 150°C and a heating rate of 10°C / min.
[0138] <Measurement of Monoester Wax Content in Toner> The content of the monoester wax in the toner can be measured using a thermal analyzer (product name: DSC Q2000, manufactured by TA Instruments Japan, Inc.). 5.0 mg of toner is placed in a sample container in an aluminum pan (KIT NO. 0219-0041), the sample container is placed on a holder unit, and set in an electric furnace. Under a nitrogen atmosphere, the sample is heated from 30°C to 200°C at a temperature increase rate of 10°C / min, and a differential scanning calorimeter (DSC) is used to measure the DSC curve, and the endothermic heat of the monoester wax in the toner is calculated. In addition, the endothermic heat of the monoester wax alone is calculated in the same manner using a 5.0 mg sample. Then, the endothermic heat of the monoester wax obtained in each measurement is used to calculate the content of the monoester wax according to the following formula. Content of monoester wax in toner (mass%)=(amount of heat absorbed by monoester wax in toner sample (J / g)) / (amount of heat absorbed by monoester wax alone (J / g))×100
[0139] <Measurement of weight average molecular weight (Mw) and peak molecular weight (Mp) of resins, etc.> The weight average molecular weight (Mw) and peak molecular weight (Mp) of a resin are measured by gel permeation chromatography (GPC) as follows. (1) Preparation of measurement samples Mix the sample with tetrahydrofuran (THF) at a concentration of 5.0 mg / mL, leave it at room temperature for 5 to 6 hours, shake thoroughly, and mix the THF and sample until the sample is no longer combined. Leave it to stand at room temperature for 12 hours or more. At this time, the time from the start of mixing the sample with THF to the end of standing is set to 72 hours or more, and the tetrahydrofuran (THF) soluble portion of the sample is obtained. Thereafter, the solution is filtered through a solvent-resistant membrane filter (pore size 0.45 μm to 0.50 μm, Myshoridisc H-25-2 [manufactured by Tosoh Corporation]) to obtain a sample solution.
[0140] (2) Measurement of samples Using the obtained sample solution, measurements are carried out under the following conditions. Equipment: High-speed GPC equipment LC-GPC 150C (Waters) Column: Shodex GPC KF-801, 802, 803, 804, 805, 806, 807 (Showa Denko Co., Ltd.) in series of 7 Mobile phase: THF Flow rate: 1.0mL / min Column temperature: 40℃ Sample injection volume: 100 μL Detector: RI (refractive index) detector In measuring the molecular weight of a sample, the molecular weight distribution of the sample is calculated from the relationship between the logarithm of a calibration curve prepared using several types of monodisperse polystyrene standard samples and the count number. The standard polystyrene samples used to create the calibration curve were made using Pressure Chemical Co. or Toyo Soda Kogyo Co., Ltd., with a molecular weight of 6.0 × 10 2 , 2.1×10 3 , 4.0×10 3 , 1.75×10 4 , 5.1×10 4 , 1.1×10 5 , 3.9×10 5 , 8.6×10 5 , 2.0×10 6 , 4.48×10 6 Use the following.
[0141] <Measurement of adhesion rate of fatty acid metal salt A> (Dispersion treatment) Add 160 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Add 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, consisting of nonionic surfactants, anionic surfactants, and organic builders, manufactured by Wako Pure Chemical Industries, Ltd.) to a centrifuge tube (volume 50 ml) to prepare a dispersion. Add 1.0 g of toner to this dispersion and break up the toner clumps with a spatula or similar. The centrifuge tube is shaken at 350 strokes per minute (strokes per minute) for 20 minutes in a shaker (Iwaki Sangyo Co., Ltd., "KM Shaker") After shaking, the solution is transferred to a glass tube for a swing rotor (capacity 50 mL) and separated in a centrifuge (H-9R, Kokusan Co., Ltd.,) at 3500 rpm for 30 minutes. Visually check that the toner and the aqueous solution are sufficiently separated, and collect the toner that has separated to the top layer with a spatula, etc. The collected aqueous solution containing the toner is filtered with a vacuum filter, and then dried in a dryer for at least 1 hour. The dried product is crushed with a spatula to obtain the toner treated with the dispersion liquid.
[0142] For the toner treated with the dispersion liquid, the amount of metal element contained in the fatty acid metal salt A is measured by fluorescent X-rays. The adhesion rate (%) of fatty acid metal salt A is calculated from the ratio of the amount of the measured element between the toner treated with the dispersion liquid and the toner before treatment. The measurement of fluorescent X-rays for each element conforms to JIS K 0119-1969, and specifically, is as follows.
[0143] The measurement equipment used was a wavelength dispersive X-ray fluorescence analyzer "Axios" (PANalytical) and the accompanying dedicated software "SuperQ ver.4.0F" (PANalytical) for setting measurement conditions and analyzing measurement data. The anode used is Rh, the measurement atmosphere is vacuum, the measurement diameter (collimator mask diameter) is 10 mm, and the measurement time is 10 seconds. In addition, when measuring light elements, a proportional counter (PC) is used, and when measuring heavy elements, a scintillation counter (SC) is used for detection.
[0144] As a measurement sample, 1 g of the toner treated with the above dispersion liquid or the toner before treatment (initial toner) is placed in a dedicated aluminum ring for pressing with a diameter of 10 mm, flattened, and pressed at 20 MPa for 60 seconds using a tablet molding compression machine "BRE-32" (manufactured by Maekawa Test Machinery Manufacturing Co., Ltd.) to form a pellet with a thickness of approximately 2 mm. Measurements are performed under the above conditions, and elements are identified based on the peak positions of the obtained X-rays, and their concentrations are calculated from the counting rate (unit: cps), which is the number of X-ray photons per unit time.
[0145] The quantitative determination method in the toner will be described by taking the case where fatty acid metal salt A is zinc stearate as an example. Add 0.5 parts by mass of zinc stearate fine powder to 100 parts by mass of toner particles, and mix thoroughly using a coffee mill. Similarly, mix 1.0 and 2.0 parts by mass of zinc stearate with the toner particles, respectively, and use these as samples for the calibration curve. For each sample, a pellet of the sample for the calibration curve is prepared as described above using a tablet molding compression machine, and the Kα ray net intensity of the metal element of the fatty acid metal salt is measured. A linear calibration curve is obtained by plotting the count rate of the line on the vertical axis and the amount of fatty acid metal salt A added in each calibration curve sample on the horizontal axis. Next, the Kα net intensity of the metal element of the fatty acid metal salt is measured using the pellets of the toner to be analyzed.Then, the content of fatty acid metal salt A in the toner is calculated from the above calibration curve.The ratio of the amount of the element of the toner treated with the above dispersion liquid to the amount of the element of the toner before treatment calculated by the above method is calculated and used as the adhesion rate (%). Adhesion rate (%) = Amount of metal elements in toner treated with dispersion liquid / Amount of metal elements in toner before treatment x 100
[0146] <Identification of hydrophobic treatment agent for magnetic material> Add 10 mL of chloroform to 100 mg of toner, and dissolve the binder resin in a homogenizer for 10 minutes. Then, collect the magnetic material using a magnet. Repeat this process several times to isolate the magnetic material. The magnetic material obtained is subjected to pyrolysis GCMS under the following conditions. The measurement results reveal the pyrolysis products of the hydrophobization agent, and the carbon number of the hydrophobization agent is determined from the main component. The pyrolysis products are detected as alkyl substituents of the hydrophobization agent, or their double bond modifications, alkylsilanes, etc. (pyrolysis GCMS) Mass spectrometer: ThermoFisherScinetific ISQ GC equipment: ThermoFisher Scientific FocusGC Ion source temperature: 250℃ Ionization method: EI Mass range: 50-1000 m / z Column: HP-5MS [30m] Pyrolysis device: Japan Analysis Industry Co., Ltd. JPS-700
[0147] <Confirmation that inorganic fine particles (magnetic materials, etc.) are unevenly distributed near the surface of toner particles> In the following cases, it is determined that "inorganic fine particles are unevenly distributed in the vicinity of the surface of the toner particles". In a cross section of a toner observed under a scanning transmission electron microscope, the area ratio of the magnetic material within a range of less than 10% of the distance from the contour of the cross section of the toner to the center of gravity (geometric center) of the cross section is defined as A. If A is 30% or more, it is determined that the inorganic fine particles are unevenly distributed near the surface of the toner particles. The procedure for observing the cross section of the toner is as follows. The toner is embedded in a visible light curable embedding resin (D-800, manufactured by Nissin EM Co., Ltd.) and cut into a 70 nm thick piece using an ultrasonic ultramicrotome (UC7, manufactured by Leica Co., Ltd.) From the obtained thin slice samples, 10 pieces whose cross-sectional diameter is within the weight average particle diameter (D4) of the toner particles ±2.0 μm are selected at random. The selected thin-film sample is stained in an atmosphere of 500 Pa of RuO4 gas for 15 minutes using a vacuum staining apparatus (VSC4R1H, manufactured by Fujifilm Corporation), and a STEM image is created using the scanning image mode of a scanning transmission electron microscope (JEM2800, manufactured by JEOL Ltd.). The STEM probe size was 1 nm, and an image was acquired with an image size of 1024 × 1024 pixels. Also, for the bright-field image, Contrast in the Detector Control panel was set to 1425, Brightness to 3750, Contrast in the Image Control panel to 0.0, Brightness to 0.5, and Gamma to 1.00 to acquire the STEM image. ast was 1425, Brightness was 3750, Image Control panel The obtained STEM image was binarized using image processing software "Image-Pro Plus (manufactured by Media Cybernetics, Inc.)" to clarify the distinction of regions of inorganic fine particles such as binder resin and magnetic material. The obtained STEM image was binarized using image processing software "Image-Pro Plus (manufactured by Media Cybernetics, Inc.)" to clarify the distinction of regions of inorganic fine particles such as binder resin and magnetic material. to clarify the distinction of regions of inorganic fine particles such as binder resin and magnetic material.
[0148] <Calculation of SP value> The SP value is determined as follows according to the calculation method proposed by Fedors. For each atom or atomic group in the molecular structure, the evaporation energy (Δei) (cal / mol) and molar volume (Δvi) (cm 3 / mol) are obtained from the table described in "Polym. Eng. Sci., 14(2), 147-154(1974)", and (ΣΔei / ΣΔvi) 0.5 is taken as the SP value (cal / cm 3 ) 0.5 and is denoted as such. Specifically, for the alkyl group, the evaporation energy (Δei) and molar volume (Δvi) are obtained respectively, and the evaporation energy is divided by the molar volume to obtain the value, which is calculated from the following formula. SP value = {(Σj × ΣΔei) / (Σj × ΣΔvi)} 0.5
[0149] <Measurement method of volume average particle diameter (Dv) and number average particle diameter (D1)> The volume average particle diameter (Dv) and number average particle diameter (D1) of the toner, toner particles, or toner base particles (hereinafter, also referred to as toner, etc.) are calculated as follows. The measuring device used is a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube. The measurement conditions and data analysis were performed using the dedicated software "Beckman Coulter The system used was "Multisizer 3 Version 3.51" (Beckman Coulter, Inc.). The measurement was performed with an effective measurement channel count of 25,000 channels. The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of 1.0%, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.). Before performing measurements and analysis, the dedicated software is set up as follows. In the "Change standard measurement method (SOMME)" screen of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard particle 10.0 μm" (Beckman Coulter, Inc.). Press the "Threshold / Noise level measurement button" to automatically set the threshold and noise level. In addition, set the current to 1,600 μA, the gain to 2, the electrolyte to ISOTON II, and check "Flush aperture tube after measurement." In the "Pulse to particle size conversion setting" screen of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.
[0150] The specific measurement method is as follows. (1) Pour 200.0 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture tube flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Put 30.0 mL of the electrolyte solution into a 100 mL flat-bottom glass beaker. Add 0.3 mL of a solution of "Contaminon N" (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion-exchanged water as a dispersant. (3) Prepare an ultrasonic disperser "Ultrasonic Dispersion System Tetra150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees and an electrical output of 120 W. Place 3.3 L of ion-exchanged water in the ultrasonic disperser's water tank and add 2.0 mL of Contaminon N to this tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While irradiating the electrolyte solution in the beaker in (4) with ultrasonic waves, 10 mg is added little by little to the above electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, drip the electrolytic solution (5) in which the toner or the like has been dispersed into the round-bottom beaker (1) placed in the sample stand to adjust the measurement concentration to 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the volume average particle size (Dv) and number average particle size (D1) are calculated. Note that when the dedicated software is set to Graph / Volume %, the "Average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen is the volume average particle size (Dv). When the dedicated software is set to Graph / Number %, the "Average diameter" on the "Analysis / Number Statistics (Arithmetic Mean)" screen is the number average particle size (D1). EXAMPLES
[0151] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to these examples. Note that the number of parts in the examples is based on mass unless otherwise specified.
[0152] <Production Example of Monoester Wax 1> Into a reaction vessel equipped with a thermometer, a nitrogen inlet tube, a stirrer, a Dean-Stark trap, and a Dimroth condenser, 100 parts of behenyl alcohol as an alcohol monomer and 80 parts of stearic acid as a carboxylic acid monomer were added, and an esterification reaction was carried out at 200°C for 15 hours. To the obtained ester compound, 20 parts of toluene and 25 parts of isopropanol were added, and 190 parts of 10% potassium hydroxide aqueous solution, which is 1.5 times the acid value of the ester compound, was added, and the mixture was stirred at 70°C for 4 hours. Then, the water tank was removed. 20 parts of ion-exchanged water was added, and the mixture was stirred at 70°C for 1 hour, after which the water tank was removed and washed. The above washing process was repeated until the pH of the removed water tank became neutral.
[0153] Thereafter, the solvent was removed under reduced pressure at 200°C and 1 kPa to obtain the final product, behenyl stearate (monoester wax 1), an ester compound of behenyl alcohol and stearic acid. The physical properties of the obtained monoester wax 1 are shown in Table 1. [Table 1] F1 indicates the carbon number of fatty acid F1, A1 indicates the carbon number of alcohol A1, and SPw is the SP value of the monoester wax.
[0154] <Production Example of Monoester Wax 2> Monoester wax 2 was obtained in the same manner as in the production example of monoester wax 1, except that the monomer was changed so as to obtain the compound shown in Table 1. The physical properties of the obtained monoester wax 2 are shown in Table 1.
[0155] <Production Example of Fatty Acid Metal Salt A1> A receiving vessel equipped with an agitator was prepared, and the agitator was rotated at 350 rpm. 500 parts of a 0.5% by mass aqueous solution of sodium stearate was added to the receiving vessel, and the liquid temperature was adjusted to 85° C. Next, 525 parts of a 0.2% by mass aqueous solution of zinc sulfate was dropped into the receiving vessel over 15 minutes. After the entire amount was charged, the mixture was aged for 10 minutes at the reaction temperature to terminate the reaction. Next, the fatty acid metal salt slurry thus obtained was filtered and washed. The fatty acid metal salt cake obtained after washing was crushed roughly, and then dried at 105°C using a continuous instantaneous airflow dryer. Then, it was pulverized using a nano grinding mill [NJ-300] (manufactured by Sunrex Co., Ltd.) under conditions of an air volume of 6.0 m3 / min and a processing speed of 80 kg / h, and then reslurried and removed fine particles and coarse particles using a wet centrifugal classifier. Then, it was dried at 80°C using a continuous instantaneous airflow dryer to obtain fatty acid metal salt fine particles A1.
[0156] The volume-based median diameter (D50s) of the obtained fatty acid metal salt A1 was 0.45 μm. The physical properties of the fatty acid metal salt A1 are shown in Table 2. [Table 2] The unit of SP value is (cal / cm 3 ) 0.5 It is.
[0157] <Production Example of Fatty Acid Metal Salt A2> In the same manner as in the production example of fatty acid metal salt A1, except that the 0.5% by mass aqueous solution of sodium stearate was replaced with a 0.5% by mass aqueous solution of sodium laurate, fatty acid metal salt A2 was obtained. The physical properties of the obtained fatty acid metal salt A2 are shown in Table 2.
[0158] <Production Example of Fatty Acid Metal Salt A3> In the same manner as in the production example of fatty acid metal salt A1, except that the 0.5% by mass aqueous sodium stearate solution was replaced with a 0.5% by mass aqueous sodium caprate solution, fatty acid metal salt A3 was obtained. The physical properties of the obtained fatty acid metal salt A3 are shown in Table 2.
[0159] <Production Example of Fatty Acid Metal Salt A4> In the same manner as in the production example of fatty acid metal salt A1, except that the 0.5% by mass aqueous solution of sodium stearate was replaced with a 0.5% by mass aqueous solution of sodium arachidate, fatty acid metal salt A4 was obtained. The physical properties of the obtained fatty acid metal salt A4 are shown in Table 2.
[0160] <Production Example of Fatty Acid Metal Salt A5> In the same manner as in the production example of fatty acid metal salt A1, except that the 0.2 mass% zinc sulfate aqueous solution was replaced with a 0.2 mass% aluminum chloride aqueous solution, fatty acid metal salt A5 was obtained. The physical properties of the obtained fatty acid metal salt A5 are shown in Table 2.
[0161] <Production Example of Fatty Acid Metal Salt-Silica Composite Particle 1> (Produced based on the composite particle production method described in JP 2018-054705 A.) Fatty acid metal salt particles Zinc stearate particles, product name: Zinc stearate, 1.5 μm, manufactured by Wako Pure Chemical Industries, Ltd., average particle size = 1.5 μm Silica particles Hydrophobically treated silica particles with a number-average primary particle size of 50 nm 100 parts of the fatty acid metal salt particles and 6.0 parts of silica fine particles were mixed and passed through a powder processing device. The mixture was blended for 10 minutes using a 3 mm clearance blender (Nobilta NOB130, manufactured by Hosokawa Micron Corporation) at a peripheral speed of 1500 rpm and cooling water flowing through the jacket. After that, coarse particles were removed using a sieve with 45 μm openings to obtain fatty acid metal salt-silica composite particles with a low coverage rate. On the other hand, fatty acid metal salt-silica composite particles with a high coverage were obtained in the same manner as in the preparation of the composite particles with a low coverage, except that the amount of silica particles was changed to 9.5 parts. Next, the fatty acid metal salt-silica composite particles with a low coverage and the fatty acid metal salt-silica composite particles with a high coverage were mixed in a mass ratio of 50:50 to obtain fatty acid metal salt-silica composite particles 1.
[0162] <Production Example of Inorganic Fine Particles 1> An aqueous solution containing ferrous hydroxide was prepared by mixing 1.0 equivalent of caustic soda solution (containing 1% by mass of sodium hexametaphosphate calculated as P relative to Fe) with an aqueous solution of ferrous sulfate. While maintaining the pH of the aqueous solution at 9, air was blown in and an oxidation reaction was carried out at 80°C to prepare a slurry liquid for generating seed crystals. Next, an aqueous solution of ferrous sulfate was added to the slurry in an amount equivalent to 1.0 relative to the initial alkali amount (sodium component of caustic soda). The pH of the slurry was maintained at 8, and the oxidation reaction was allowed to proceed while blowing in air. At the end of the oxidation reaction, the pH was adjusted to 6, and the slurry was washed with water and dried to obtain magnetic iron oxide, which was spherical magnetite particles and had a number-average particle size of the primary particles of 200 nm.
[0163] 10.0 kg of the magnetic iron oxide was put into a Mixmuller (Model MSG-0L, manufactured by Shinto Kogyo Co., Ltd.) and subjected to a crushing treatment for 30 minutes. Then, 95 g of n-decyltrimethoxysilane was added as a silane coupling agent to the device, and the device was operated for 1 hour to hydrophobize the particle surfaces of the magnetic iron oxide with the silane coupling agent, thereby obtaining inorganic fine particles 1 (magnetic material). The physical properties of inorganic fine particles 1 are shown in Table 3. [Table 3] The alkyl substituent column indicates the number of carbon atoms in the alkyl group of the surface treatment agent for the magnetic material. The unit of SP value is (cal / cm 3 ) 0.5 It is.
[0164] <Production Examples of Inorganic Fine Particles 2 and 3> Inorganic fine particles 2 and 3 were obtained in the same manner as in the production example of inorganic fine particles 1, except that the hydrophobizing treatment agent was changed as shown in Table 3.
[0165] <Production Example of Vinyl Resin 1> The following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. Solvent: Toluene 100.0 parts Monomer composition 100.0 parts (The monomer composition is a mixture of styrene, n-butyl acrylate, and divinylbenzene in the ratios shown below.) (Styrene 78.0 parts) (n-Butyl acrylate 22.0 parts) (divinylbenzene 0.50 parts) Polymerization initiator 0.50 parts t-Butyl peroxypivalate (NOF Corp.: Perbutyl PV) The inside of the reaction vessel was heated to 70°C while stirring at 200 rpm, and a polymerization reaction was carried out for 12 hours, to obtain a solution in which a polymer of the monomer composition was dissolved in toluene. The solution was then cooled to 25°C, and then poured into 1000.0 parts of methanol while stirring, to precipitate the methanol insoluble matter. The obtained methanol insoluble matter was filtered, washed with methanol, and then vacuum dried at 40°C for 24 hours to obtain vinyl resin 1. The weight average molecular weight (Mw) of vinyl resin 1 was 21,000.
[0166] <Production Example of Toner Particle 1> 450 parts of 0.1 mol / L-Na3PO4 aqueous solution was added to 720 parts of ion-exchanged water and heated to 60° C., after which 67.7 parts of 1.0 mol / L-CaCl2 aqueous solution was added to obtain an aqueous medium containing a dispersion stabilizer. Styrene: 78.0 parts n-Butyl acrylate: 22.0 parts Divinylbenzene: 0.50 parts ·Inorganic fine particles 1: 65.0 parts The above formulation was uniformly dispersed and mixed using an attritor (Nippon Coke and Engineering Co., Ltd.). The obtained monomer composition was heated to a temperature of 60° C., and the following materials were mixed and dissolved therein to obtain a polymerizable monomer composition. Hydrocarbon wax: 6.0 parts (Fischer-Tropsch wax (HNP-51: manufactured by Nippon Seiro Co., Ltd.)) Monoester wax 1: 20.0 parts Polymerization initiator: 10.0 parts (t-Butyl peroxypivalate (25% toluene solution)) Negative charge control agent T-77 (manufactured by Hodogaya Chemical Co., Ltd.): 1.0 part The polymerizable monomer composition was added to the aqueous medium, and the mixture was stirred at 12,000 rpm for 15 minutes in a nitrogen atmosphere at a temperature of 60°C using a TK homomixer (Tokushu Kika Kogyo Co., Ltd.) to form granules. Thereafter, the mixture was stirred with a paddle impeller and the polymerization reaction was carried out at a reaction temperature of 70° C. for 300 minutes. After the reaction was completed, the suspension was heated to 100°C and maintained for 2 hours. Thereafter, as a cooling step, 0°C water was added to the suspension and the suspension was cooled from 98°C to 30°C at a rate of 200°C / min, and then maintained at 55°C for 3 hours. Thereafter, the suspension was naturally cooled to 25°C at room temperature. The cooling rate was 2°C / min. Thereafter, hydrochloric acid was added to the suspension and the suspension was thoroughly washed to dissolve the dispersion stabilizer, and the suspension was filtered and dried to obtain toner particles 1.
[0167] <Production Examples of Toner Particles 2, 3, 5, and 6> Toner particles 2, 3, 5 and 6 were obtained in the same manner as in the production example of toner particles 1, except that inorganic fine particles 1, monoester wax 1, colorant and release agent were changed as shown in Table 4. [Table 4] The column of inorganic fine particle shells was marked as "present" when the inorganic fine particles were unevenly distributed near the surface of the toner particles to form a shell state, and marked as "absent" when the inorganic fine particles were not unevenly distributed near the surface of the toner particles.
[0168] <Production Example of Toner Particle 4> Toner particles 4 were obtained in the same manner as in the production example of toner particles 1, except that 65.0 parts of inorganic fine particles 1 were changed to 7.0 parts of carbon black (manufactured by Mitsubishi Chemical, product name: #25B).
[0169] <Production Example of Toner Particle 7> (Pulverization) Vinyl resin 1: 100.0 parts Monoester wax 1: 20.0 parts ·Inorganic fine particles 1: 65.0 parts Hydrocarbon wax: 6.0 parts (Fischer-Tropsch wax (HNP-51: manufactured by Nippon Seiro Co., Ltd.)) The above materials were premixed in a Henschel mixer (manufactured by Nippon Coke Company), and then melt-kneaded using a twin-screw kneading extruder (manufactured by Ikegai Iron Works: PCM-30 type). The obtained kneaded product was cooled, coarsely pulverized with a hammer mill, and then pulverized with a mechanical pulverizer (Turbo Kogyo Co., Ltd.: T-250). The obtained finely pulverized powder was classified with a multi-division classifier utilizing the Coanda effect, and toner particles 7 having a volume average particle size (Dv) of 7.4 μm were obtained.
[0170] <Toner 1 Manufacturing Example> To 100 parts of toner particles 1, 0.50 parts of hydrophobically treated silica fine particles having a number average primary particle size of 50 nm were added as an external additive, and external addition mixing treatment 1 was performed by mixing for 11 minutes at 2970 rpm using a Henschel mixer FM10C (HM) (Nippon Coke & Co., Ltd.). Thereafter, 0.10 parts of fatty acid metal salt A1 was further added, and the mixture was mixed for 1 minute at 2970 rpm using a Henschel mixer FM10C, thereby carrying out an external addition mixing treatment 2.
[0171] Thereafter, further, external addition mixing treatment 3 was carried out using the device shown in FIG. The configuration of the apparatus shown in FIG. 1 is such that the inner diameter of the main casing 31 is 130 mm, and the volume of the processing space 39 is 2.0×10 -3 m 3 The device used was one shown in Fig. 2, with the rated power of the drive unit 38 being 5.5 kW, and the shape of the stirring blade 33 being that shown in Fig. 2. The overlap width d of the stirring blade 33a and the stirring blade 33b in Fig. 2 was set to 0.25D with respect to the maximum width D of the stirring blade 33, and the clearance between the stirring blade 33 and the inner circumference of the main casing 31 was set to 6.0 mm. 1 having the above configuration, 740 g of toner particles that had been subjected to external addition mixing process 2 were put into the apparatus, and external addition mixing process 3 was performed. The conditions for external addition mixing process 3 were that the peripheral speed of the outermost end of the stirring blade 33 was adjusted so that the rotation speed of the drive unit 38 was constant at 1100 rpm, and the processing time was 3 minutes.
[0172] After the external addition mixing process 3, coarse particles were removed using a circular vibrating sieve equipped with a screen having a diameter of 500 mm and an opening of 75 μm to obtain Toner 1. The external addition conditions for Toner 1 are shown in Table 5, and the physical properties are shown in Table 6. [Table 5]
[0173] [Table 6]
[0174] <Production Examples of Toners 2 to 23> Toners 2 to 23 were produced in the same manner as in the production example of toner 1, except that the type and amount of external additive, toner particles, external addition device, and external addition conditions were changed as shown in Table 5. The physical properties of the obtained toner are shown in Table 6. The evaluation methods and evaluation criteria are explained below. The evaluation results for each toner are shown in Table 7.
[0175] The evaluation was carried out using a commercially available color laser printer (HP LaserJet Enterprise Color M611dn, manufactured by HP) that had been partially modified so that it could operate even with only one color process cartridge installed, and so that the process speed was faster than the original speed. The toner was removed from the cyan cartridge and replaced with 325 g of the toner to be evaluated. The cyan cartridge filled with the toner to be evaluated was mounted in the main body, and the evaluation was performed without mounting any cartridges other than the cyan cartridge.
[0176] <Low temperature fixability> The image forming apparatus and toner cartridge were left in a low temperature and low humidity environment (15°C / 10% RH: hereinafter referred to as LL environment) for 48 hours. Then, a density check image (solid image) was output while changing the fixing temperature, and the fixing temperature was confirmed. The lowest temperature at which cold offset did not occur was taken as the fixing temperature, and it was evaluated according to the following criteria. A: Fixing temperature below 170℃ B: Fixing temperature 170℃ or higher and less than 180℃ C: Fixing temperature 180℃ or higher and less than 190℃ D: Fixing temperature 190℃ or higher
[0177] <Paper sticking after fixing> The image forming apparatus and toner cartridge were left in a high temperature and high humidity environment (32.5°C / 80% RH: hereinafter referred to as HH environment) for 48 hours. Then, 100 solid images were output continuously, and the images were left on the output tray for 10 minutes, after which the images were checked for sticking. A: No sticking is observed. B: Slight sticking is observed. C: Sticking is observed. D: It sticks and is difficult to remove
[0178] <Development streaks> After the evaluation of the solid image density was completed, the images were printed on LETTER size XEROX4200 paper (XEROX, 75 g / m2) in a high temperature and high humidity environment (32.5°C / 80% RH: hereinafter referred to as HH environment). 2) and halftone (toner load: 0.3mg / cm 2 The halftone image was printed out and observed for the presence or absence of vertical streaks in the paper ejection direction, and the development streaks were evaluated as follows. A: Not occurred B: Vertical stripes in the paper ejection direction appear in 1 to 3 places on the halftone image. C: Four to six vertical streaks in the ejection direction appear on the halftone image. D: Seven or more vertical stripes appear in the halftone image in the paper ejection direction, or the width is 0.5 mm or more.
[0179] <Solid image density> The image forming apparatus and toner cartridge were left in a high temperature and high humidity environment (32.5°C / 80% RH: hereinafter referred to as HH environment) for 48 hours. Then, 15,000 images with a print rate of 1% were printed. After that, a density check image (solid image) was printed to check the image density. A: Image density 1.40 or higher B: Image density 1.35 or more and less than 1.40 C: Image density 1.30 or more and less than 1.35 D: Image density less than 1.30
[0180] <Drop> The image forming apparatus and toner cartridge were left in a high temperature and humidity environment (15°C / 10% RH: hereinafter referred to as LL environment) for 48 hours. Then, 15,000 images with a printing rate of 1% were printed. After that, halftone images were printed and toner dripping was confirmed. A: No dripping occurs on the image. B: Less than 10 spots of dripping on the image C: There are 10 or more but less than 30 drips on the image. D: More than 30 drips on the image
[0181] [Table 7]
[0182] The present disclosure relates to the following configurations and methods. (Configuration 1) A toner having toner particles containing a binder resin, the toner particles contain a monoester wax; A fatty acid metal salt A is present on the surface of the toner particles, The coverage rate of the surface of the toner particle with the fatty acid metal salt A, which is determined by X-ray photoelectron spectroscopy, is defined as X(A); When the coverage rate of the surface of the toner particle with the fatty acid metal salt A, which is determined by image analysis using a scanning electron microscope, is S(A), A toner characterized in that X(A) and S(A) satisfy the following formulae (1), (2) and (3): S(A)≧0.03 (1) X(A)≦0.250 (2) 0.248≦S(A) / X(A)≦1.000 (3) (Configuration 2) the monoester wax being a condensate of a fatty acid F1 and an alcohol A1, The fatty acid metal salt A is a salt of fatty acid F2 and a metal, The fatty acid F2 has 12 to 18 carbon atoms, At least one of the following (a) and (b) is satisfied: (a) the difference between the carbon number of the fatty acid F1 and the carbon number of the fatty acid F2 is 2 or less; (b) the difference between the carbon number of the alcohol A1 and the carbon number of the fatty acid F2 is 2 or less; 2. The toner according to claim 1. (Configuration 3) The fatty acid F1 is an aliphatic monocarboxylic acid having 16 to 22 carbon atoms, The alcohol A1 is an aliphatic monoalcohol having 16 to 24 carbon atoms. 3. The toner according to configuration 2. (Configuration 4) The toner according to Configuration 2 or 3, wherein the valence of the metal in the fatty acid metal salt A is divalent or greater. (Configuration 5) 5. The toner according to any one of configurations 1 to 4, wherein the fatty acid metal salt A is at least one compound selected from the group consisting of zinc stearate and aluminum stearate. (Configuration 6) The toner according to any one of configurations 1 to 5, wherein the toner particles contain inorganic fine particles. (Configuration 7) 7. The toner according to embodiment 6, wherein the inorganic fine particles are surface-treated with a treatment agent having an alkyl group having 4 to 20 carbon atoms. (Configuration 8) The toner according to Configuration 7, wherein the inorganic fine particles are unevenly distributed in the vicinity of the surface of the toner particles. (Method 9) a charging step of charging the surface of the electrostatic latent image bearing member; an electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the electrostatic latent image bearing member; a developing step of developing the electrostatic latent image with a toner to form a toner image on the surface of the electrostatic latent image carrier; a transfer step of transferring the toner image from the electrostatic latent image carrier to a transfer material with or without an intermediate transfer member; and a fixing step of fixing the toner image transferred onto the transfer material by a heating and pressing means; An image forming method comprising: The toner is a toner according to any one of configurations 1 to 8, The developing step is a one-component contact developing step. 1. An image forming method comprising: (Method 10) A method for producing the toner according to any one of configurations 1 to 8, comprising the steps of: a treatment step of treating a mixture containing the toner particles and the fatty acid metal salt A, The processing device used in the processing step is An agitating member having a rotor and a plurality of agitating blades provided on a surface of the rotor; A container having a cylindrical inner circumferential surface that accommodates the stirring member; and a drive unit for applying a rotational drive force to the rotor to rotate the stirring member within the container, The plurality of stirring blades are provided so as to have a gap between each of them and an inner peripheral surface of the container, The plurality of stirring blades include a first stirring blade for feeding the mixture introduced into the container in one axial direction of the rotor by rotation of the stirring member, and a second stirring blade for feeding the mixture in the other axial direction of the rotor. A method for producing a toner comprising the steps of:
Claims
1. A toner having toner particles containing a binder resin, the toner particles contain a monoester wax; A fatty acid metal salt A is present on the surface of the toner particles, The coverage rate of the surface of the toner particle with the fatty acid metal salt A, which is determined by X-ray photoelectron spectroscopy, is represented by X(A); When the coverage rate of the surface of the toner particle with the fatty acid metal salt A, which is determined by image analysis using a scanning electron microscope, is S(A), A toner characterized in that X(A) and S(A) satisfy the following formulas (1), (2) and (3). S(A)≧0.03...(1) X(A)≦0.250...(2) 0.248≦S(A) / X(A)≦1.000...(3)
2. the monoester wax is a condensate of a fatty acid F1 and an alcohol A1, The fatty acid metal salt A is a salt of fatty acid F2 and a metal, The fatty acid F2 has 12 to 18 carbon atoms, At least one of the following (a) and (b) is satisfied: (a) the difference between the carbon number of the fatty acid F1 and the carbon number of the fatty acid F2 is 2 or less; (b) the difference between the carbon number of the alcohol A1 and the carbon number of the fatty acid F2 is 2 or less; The toner according to claim 1 .
3. The fatty acid F1 is an aliphatic monocarboxylic acid having 16 to 22 carbon atoms, The alcohol A1 is an aliphatic monoalcohol having 16 to 24 carbon atoms. The toner according to claim 2.
4. 3. The toner according to claim 2, wherein the valence of the metal in the fatty acid metal salt A is divalent or greater.
5. 5. The toner according to claim 1, wherein the fatty acid metal salt A is at least one compound selected from the group consisting of zinc stearate and aluminum stearate.
6. The toner according to any one of claims 1 to 4, wherein the toner particles contain inorganic fine particles.
7. 7. The toner according to claim 6, wherein the inorganic fine particles are surface-treated with a treatment agent having an alkyl group having 4 to 20 carbon atoms.
8. The toner according to claim 7 , wherein the inorganic fine particles are unevenly distributed in the vicinity of the surface of the toner particles.
9. a charging step of charging the surface of the electrostatic latent image bearing member; an electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the electrostatic latent image bearing member; a developing step of developing the electrostatic latent image with a toner to form a toner image on the surface of the electrostatic latent image carrier; a transfer step of transferring the toner image from the electrostatic latent image carrier to a transfer material with or without an intermediate transfer member; and a fixing step of fixing the toner image transferred onto the transfer material by a heating and pressing means; An image forming method comprising: The toner is the toner according to any one of claims 1 to 4, The developing step is a one-component contact developing step.
1. An image forming method comprising:
10. A method for producing the toner according to any one of claims 1 to 4, comprising the steps of: a treatment step of treating a mixture containing the toner particles and the fatty acid metal salt A, The processing device used in the processing step is An agitating member having a rotor and a plurality of agitating blades provided on a surface of the rotor; A container having a cylindrical inner circumferential surface that accommodates the stirring member; and a drive unit for applying a rotational drive force to the rotor to rotate the stirring member within the container, The plurality of stirring blades are provided so as to have a gap between each of them and an inner peripheral surface of the container, The plurality of stirring blades include a first stirring blade for feeding the mixture introduced into the container in one axial direction of the rotor by rotation of the stirring member, and a second stirring blade for feeding the mixture in the other axial direction of the rotor. A method for producing a toner comprising the steps of:
Citation Information
Patent Citations
Toner
JP2015225319A
Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
JP2018054705A
Toner
JP2021009250A